Silica-supported polyolefin catalyst system
The preparation of spherical single-particle gel silica particles through a water-in-oil emulsion method solves the problem of easy agglomeration of silica carrier particles in the existing technology and improves the performance and polymerization activity of the catalyst.
Patent Information
- Application Number
- CN202380040927.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-16
- Filing Date
- 2023-03-14
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, silica support particles are often non-spherical, resulting in agglomeration, reducing catalyst performance, and making spherical single-particle gel silica particles that have both high pore volume and high surface area difficult to prepare.
The water-in-oil emulsion method is used to prepare spherical single-particle gel silica particles. By controlling the conditions of the emulsion method, including the formation of silica sol, the mixing and gelation process of the emulsion, the particle size, pore volume and surface area of the particles are adjusted. .
The prepared silica particles have a suitable combination of particle size, pore volume and surface area, which improves the catalyst loading and activity during the polymerization process, reduces static electricity accumulation, and reduces the usage of antistatic agents.
Smart Images

Figure BDA0005136970530000081 
Figure BDA0005136970530000082 
Figure BDA0005136970530000091
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of priority to U.S. Provisional Patent Application No. 63 / 320,579, filed on March 16, 2022, which is hereby incorporated by reference in its entirety for any and all purposes. Background Art
[0003] Polyolefins are usually prepared by reacting olefin monomers in the presence of a catalyst consisting of a support and catalytic components deposited in the pores of the support and on the surface of the support. For example, typical polyolefin catalysts include Ziegler-Natta catalysts, metallocene catalysts and chromium catalysts, all of which may contain a support material.
[0004] The properties of the resulting polymer are highly dependent on the catalyst, so changes in the characteristics of the catalyst will result in changes in, for example, molecular weight, melt index, bulk density, particle shape, particle size, particle size distribution, and reaction temperature that can be used to affect polymerization. In addition, the properties of the catalyst and its performance are highly dependent on the properties of the material used to support the catalyst. The properties of the support, in turn, depend on its preparation method.
[0005] Silica carriers are reused because they form highly active polymerization catalysts. A known method for forming silica carrier particles is by grinding silica gel and spray drying the ground particles. Certain properties of silica particles, such as surface area, pore structure and particle size, can be affected by controlling the grinding and spray drying process. In this way, the properties of silica carriers can be controlled to adapt to various catalyst components and desired polymer types. However, conventional spray-dried silica carrier particles also have disadvantages. For example, they are often non-spherical, and the agglomeration of particles will reduce catalyst performance. Therefore, there is a need for a spherical silica-loaded polyolefin catalyst made of non-agglomerated carrier particles, the carrier particles having a surface area and pore structure suitable for polyolefin catalysts. Summary of the invention
[0006] The present disclosure generally relates to an olefin catalyst system comprising a silica support. For example, in one embodiment, the olefin polymerization catalyst system comprises a silica support, a catalyst precursor compound, and an activator. The silica support comprises a plurality of silica gel particles. Each particle comprises a rigid network of amorphous silica. The particles are spherical single-particle gel particles having an average aspect ratio of about 1.2 or less, an average pore volume of about 1.4 ml / g to about 3 ml / g, and a diameter of about 200 m 2 / g to about 950m 2 The average surface area is about 100 μm / g and the median particle size is about 4 μm to about 100 μm.
[0007] In another embodiment, the olefin polymerization catalyst system comprises a silica support and a chromium compound. The silica support comprises a plurality of silica gel particles. Each particle comprises a rigid network of amorphous silica. The particles are spherical single-particle gel particles having an average aspect ratio of about 1.2 or less, an average pore volume of about 1.4 ml / g to about 3 ml / g, and about 200 m 2 / g to about 950m 2 The average surface area is about 100 μm / g and the median particle size is about 4 μm to about 100 μm.
[0008] In another embodiment, the olefin polymerization catalyst system comprises a silica support, a magnesium halide, a transition metal compound, an alkyl aluminum cocatalyst, and an electron donor compound. The silica support comprises a plurality of silica gel particles. Each particle comprises a rigid network of amorphous silica. The particles are spherical single-particle gel particles having an average aspect ratio of about 1.2 or less, an average pore volume of about 1.4 ml / g to about 3 ml / g, and about 200 m 2 / g to about 950m 2 The average surface area is about 100 μm / g and the median particle size is about 4 μm to about 100 μm.
[0009] A method for polymerizing olefins is also described. The method includes contacting an olefin monomer with a catalyst system comprising a silica support and a catalyst precursor compound to form polyolefin particles. The silica support comprises a plurality of silica gel particles. Each particle comprises a rigid network of amorphous silica. The particles are spherical single-particle gel particles having an average aspect ratio of about 1.2 or less, an average pore volume of about 1.4 ml / g to about 3 ml / g, and about 200 m 2 / g to about 950m 2 The average surface area is about 100 μm / g and the median particle size is about 4 μm to about 100 μm.
[0010] Other features and other aspects of the disclosure are discussed in more detail below. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 A process flow chart of the production method according to the present disclosure is shown.
[0012] Figure 2 An SEM image of the silica particles produced in Example 1 is shown.
[0013] Figure 3 An SEM image of the silica particles produced in Example 2 is shown.
[0014] Figure 4 An SEM image of the silica particles produced in Example 3 is shown.
[0015] Figure 5 An SEM image of the polymer produced in Example 11 is shown.
[0016] Figure 6 Shown is an SEM image of the polymer produced using the catalyst from Example 14B.
[0017] Figure 7 Shown is a SEM image of the polymer produced using the catalyst from Example 15B.
[0018] Figure 8 Shown is an SEM image of the polymer produced using the catalyst from Example 16B.
[0019] Fig. 9 Shown is an SEM image of the polymer produced using the catalyst from Example 16C.
[0020] Fig.10 An SEM image of the polymer produced in Example 24 is shown.
[0021] Fig.11 An SEM image of the polymer produced in Example 25 is shown. DETAILED DESCRIPTION
[0022] Various embodiments are described below. It should be noted that the specific embodiments are not intended to be exhaustive or limit the broader aspects discussed herein. An aspect described in conjunction with a specific embodiment is not necessarily limited to that embodiment and can be practiced with any other (one or more) embodiments.
[0023] As used herein with respect to numerical ranges, the terms "about," "approximately," "substantially," and similar terms will be understood by one of ordinary skill in the art and will vary to some extent depending on the context in which it is used. If the use of a term is unclear to one of ordinary skill in the art, the terms will be plus or minus 10% of the disclosed numerical values, taking into account the context in which it is used. When "about," "approximately," "substantially," and similar terms are applied to structural features (e.g., describing their shape, size, position, orientation, etc.), these terms are intended to cover minor changes in structure that may be caused by, for example, manufacturing or assembly processes, and are intended to have a broad meaning consistent with the common and recognized usage of one of ordinary skill in the art to which the subject matter of the present disclosure belongs. Therefore, these terms should be interpreted as indicating that non-substantial or insignificant modifications or changes to the subject matter described and claimed are considered to be within the scope of the present disclosure as described in the appended claims.
[0024] In the context of describing elements (especially in the context of the following claims), the use of the terms "a", "an", "the", and similar references should be interpreted as covering both the singular and the plural, unless otherwise specified herein or the context is clearly contradictory. Unless otherwise specified herein, the enumeration of numerical ranges herein is intended only as a shorthand method for individually citing each individual value within the range, and each individual value is incorporated into the specification as if it were individually listed herein. Unless otherwise specified herein or the context is clearly contradictory, all methods described herein can be performed in any suitable order. Unless otherwise specified, the use of any and all examples or exemplary language (e.g., "such as") provided herein is intended only to better illustrate the embodiments without limiting the scope of the claims. Any language in the specification should not be interpreted as indicating that any unclaimed element is required.
[0025] In general, the present disclosure relates to an olefin catalyst system comprising a silica support formed of spherical single-particle gel silica particles having a combination of particle size, pore volume, and surface area that is particularly suitable for use as a catalyst support. The spherical shape and single-particle gel nature of the particles provide various advantages over conventional silica supports, such as silica supports formed by spray drying agglomeration methods.
[0026] For example, in olefin polymerization processes, catalysts containing single-particle gel support particles tend to perform better than catalysts containing agglomerated support particles. As used herein, single-particle gel particles refer to particles that are not formed by agglomerates of smaller particles. Agglomerates refer to products formed by a combination of particles held together by various physical-chemical forces. More specifically, agglomerates are composed of multiple adjacent component primary particles that are bonded and connected at their contact points. Unlike agglomerates, single-particle gel particles cannot be separated into smaller particles without breaking the particles.
[0027] In addition, because the particles are highly spherical, they tend to be less susceptible to static buildup when used in a gas phase polymerization process than particles of lower sphericity. Thus, using the catalysts described herein in a gas phase olefin polymerization process can reduce or possibly eliminate the amount of antistatic agent required in the polymerization vessel.
[0028] As mentioned above, the particles also have a combination of pore volume, surface area and particle size that is particularly suitable for supporting catalyst components and for use in olefin polymerization processes. For example, the particles have a relatively high surface area as determined by the BET method using nitrogen adsorption as described below. Typically, the average surface area of the particles is about 200 m 2 / g or greater, in some embodiments about 400m 2 / g or greater, in some embodiments about 500m 2 / g or greater, in some embodiments about 600m 2 / g or greater, in some embodiments about 700m 2 / g or more. Typically, the average surface area of the particles is about 950m 2 / g or less, in some embodiments about 800m 2 / g or less, in some embodiments about 700m 2 / g or less, in some embodiments about 600m 2 / g or less, in some embodiments about 500m 2 / g or less.
[0029] The particles also have a relatively high pore volume as measured by nitrogen pore volume as described below. For example, the average pore volume of the particles is typically about 1.4 cc / g or greater, in some embodiments about 1.8 cc / g or greater, in some embodiments about 2 cc / g or greater, and in some embodiments about 2.25 cc / g or greater. Typically, the pore volume is about 3 cc / g or less, in some embodiments about 2.6 cc / g or less, in some embodiments about 2.25 cc / g or less, and in some embodiments about 2 cc / g or less.
[0030] The carrier particles can also have a pore size suitable for loading a specific catalyst component on the particles. For example, it may be desirable for some catalyst components or activators to enter the pores of the carrier. In this respect, the average pore size (as measured by nitrogen porosimetry) of the pores on the carrier particles can be relatively large, for example, about 30 angstroms or larger, about 50 angstroms or larger in some embodiments, about 70 angstroms or larger in some embodiments, about 100 angstroms or larger in some embodiments, about 150 angstroms or larger in some embodiments. Typically, the average pore size is about 300 angstroms or smaller, about 250 angstroms or smaller in some embodiments, and about 200 angstroms or smaller in some embodiments.
[0031] The surface area was determined by BET nitrogen adsorption analysis after the sample was activated under vacuum for 30 minutes at 400°C. The surface area was calculated from multiple point values of nitrogen volume absorption during the adsorption branch at low [P / Po = ~0.05 to 0.15] partial pressures. The adsorption branch of the isotherm stopped at a partial pressure of P / Po = 0.995, and the descending branch of the isotherm was then measured. The nitrogen pore volume was calculated by applying the Gurvich rule at P / Po = 0.995. The pore size is reported as the calculated BJH desorption average diameter.
[0032] In the past, it has been difficult to produce spherical single-particle gel silica particles that have both high pore volume and high surface area. However, in some embodiments, the silica particles described herein have an average pore volume of about 2.3 cc / g or greater and a surface area greater than about 350 m 2 This combination allows high catalyst loading on the support and high catalytic activity during the polymerization process.
[0033] The particle size that is intended to be imparted to the support particles depends on the type of polymerization reaction for which the final supported catalyst is used. Typically, the median particle size (D50) of the particles as measured by the laser diffraction method described below is about 4 μm or greater, in some embodiments about 10 μm or greater, in some embodiments about 20 μm or greater, in some embodiments about 30 μm or greater, in some embodiments about 50 μm or greater. The median particle size is typically about 100 μm or less, in some embodiments about 75 μm or less, in some embodiments about 50 μm or less.
[0034] Regardless of their average size, the particles can have a relatively narrow size distribution. The width of the particle size distribution can be measured as the distribution span, defined by the following equation: Where D 10 , D 50 and D 90 They represent the 10th, 50th and 90th percentiles of the particle size (diameter) distribution, i.e., D 90 Meaning that 90% by volume of the particles have a diameter less than or equal to 100 microns. In this regard, the distribution span of the particles may be about 1.5 or less, in some embodiments about 1.45 or less, in some embodiments about 1.4 or less, in some embodiments about 1.3 or less, and in some embodiments from about 0.9 to about 1.25. The narrow particle size distribution also helps reduce static forces when used in a gas phase polymerization process.
[0035] The silica particles disclosed herein can be prepared by a water-in-oil emulsion method. The inventors unexpectedly discovered that the emulsion method described herein can produce silica particles with the above-mentioned unique properties. In addition, it has been discovered that the particle size, particle size distribution, pore size, pore volume and surface area of the particles can be controlled by manipulating certain aspects of the emulsion method.
[0036] In the water-in-oil emulsion method, silica sol is first prepared by mixing an alkali metal silicate with an acid. The sol is then mixed with oil and a surfactant to form an emulsion. In the emulsion formed in this process, the oil phase is continuous and the sol forms stable spherical droplets dispersed in the oil phase. The pH can then be adjusted by adding an alkaline compound to the emulsion, which can help control the gelation process and the final pore structure in the emulsion.
[0037] refer to Figure 1 The method is described in more detail. First, in step 101, a silica sol is formed by mixing an inorganic acid and an alkali metal silicate. The alkali metal silicate may include sodium silicate, potassium silicate, lithium silicate, etc. The alkali metal silicate is generally provided in an aqueous solution at a concentration of about 5 wt % to about 50 wt % (based on the SiO in the alkali metal silicate). 2 ), such as about 10% by weight to about 35% by weight. The inorganic acid can be sulfuric acid, hydrochloric acid, nitric acid, etc. In some embodiments, the alkali metal silicate is sodium silicate, and the inorganic acid is sulfuric acid. In other embodiments, the alkali metal silicate is sodium silicate, and the inorganic acid is hydrochloric acid. In order to form a sol, the alkali metal silicate can be added to a container containing the inorganic acid. The flow rate is adjusted to obtain the desired output of the industrial scale. For example, under laboratory scale, the alkali metal silicate can be added to the inorganic acid with a flow rate of about 1ml / min to about 250ml / min, such as about 5ml / min to about 200ml / min, preferably about 50ml / min to about 200ml / min. Alternatively, the alkali metal silicate and the inorganic acid can be mixed once by pouring one into the other. The concentration of the inorganic acid is generally about 10% by weight to about 50% by weight, about 15% by weight to about 40% by weight in some embodiments, and about 18% by weight to about 35% by weight in some embodiments. The weight ratio of inorganic acid to alkali metal silicate preferably results in a pH of less than 7. The weight ratio of inorganic acid to alkali metal silicate is generally from about 1:10 to about 2:1, in some embodiments from about 1:7 to about 1:1, and in some embodiments from about 1:5 to about 1:2.
[0038] In some embodiments, the concentration and amount of aqueous alkali metal silicate and inorganic acid are selected to achieve a specified pH value. For example, in some embodiments, the pH of the resulting mixture is controlled to remain below about 4, such as below about 3, such as below about 1.5. The pH of the resulting mixture is typically about 1 or greater.
[0039] During the sol formation step, the temperature should be controlled at a relatively low temperature. For example, in some embodiments, the temperature is controlled at about 40°C or lower, in some embodiments, about 30°C or lower, and in some embodiments, about 20°C or lower.
[0040] In order to form a colloidal sol, a mixer (such as a static mixer or an in-line mixer) can be used to continuously mix inorganic acid and alkali metal silicate in a container. The mixer can be enough to form a colloidal sol at any suitable speed. For example, in some embodiments, the mixture can be mixed for about 2 minutes to about 1 hour, such as about 5 minutes to about 45 minutes, such as about 10 minutes to about 40 minutes.
[0041] After forming the colloidal sol, it is pumped into or otherwise mixed with oil and surfactant to form a water-in-oil emulsion in step 102. Oil and surfactant can be mixed to form a surfactant / oil mixture, and the mixture is added to the colloidal sol. The amount of surfactant can be controlled to form a stable spherical silica sol droplet. In some embodiments, the amount of surfactant in the mixture is about 3 weight % to about 25 weight % of the total surfactant / oil mixture. Preferably, the amount of surfactant in the mixture is about 5 weight % to about 15 weight %. Alternatively, oil and surfactant are added to the colloidal sol respectively in an amount sufficient to provide a surfactant / oil mixture with the above-mentioned weight percentage.
[0042] The oil is not particularly limited except that it should be non-reactive and immiscible with aqueous alkali metal silicates and inorganic acids. Exemplary oils include n-octane, gasoline, kerosene, isoparaffin oils, etc., alicyclic hydrocarbons such as cyclononane, cyclodecane, etc., aromatic hydrocarbons such as toluene, xylene, ethylbenzene, tetralin, etc., and alkane mixtures such as mineral oil.
[0043] A wide range of surfactants can be used including: caprylic acid glyceryl, monolauric acid glyceryl, mono / dicocoic acid glyceryl, dilauric acid glyceryl, monostearate glyceryl, distilled monostearate glyceryl, distearate glyceryl, monooleate glyceryl, dioleate glyceryl, trioleate glyceryl, monoisostearate glyceryl, monoricinoleate glyceryl, monohydroxystearate glyceryl, POE monostearate glyceryl, acetylated monostearate glyceryl, succinylated monostearate glyceryl, diethyl Acylated tartaric acid monostearate, modified phthalic acid glyceryl resin, monostearate triglyceride, monooleate triglyceride, monoisostearate triglyceride, tetraoleate decaglycerol, decaglycerol decaglycerol, pentaerythritol monolaurate, monostearate pentaerythritol, distearate pentaerythritol, tetrastearate pentaerythritol, monooleate pentaerythritol, dioleate pentaerythritol, trioleate pentaerythritol, tetraricinoleate pentaerythritol, monolaurate sorbitan ester, POE monolaurate Sorbitan cinnamate, sorbitan monopalmitate, POE sorbitan monopalmitate, sorbitan monostearate, POE sorbitan monostearate, sorbitan tristearate, POE sorbitan tristearate, sorbitan monooleate, POE sorbitan monooleate, sorbitan sesquioleate, sorbitan trioleate, POE sorbitan trioleate, POE sorbitan trioleate, POE sorbitan hexaoleate, POE sorbitan laurate oleate, POE sorbitan polyoleate Esters, POE sorbitol, beeswax esters, sucrose monolaurate, sucrose cocoate, sucrose monomyristate, sucrose monopalmitate, sucrose dipalmitate, sucrose monostearate, sucrose distearate, sucrose monooleate, sucrose dioleate, lauryl lactate, cetyl lactate, sodium lauryl lactylate, sodium stearoyl lactylate, sodium isostearyl-2-lactylate, sodium stearoyl-2-lactylate, calcium stearoyl-2-lactylate, sodium capryl lactate, lauryl alcohol, and cetyl alcohol.
[0044] In one embodiment, the surfactant comprises at least one sorbitan ester. Sorbitan esters include sorbitan fatty acid esters, wherein the fatty acid component of the ester includes a carboxylic acid having from about 10 to about 100 carbon atoms, and in one embodiment, from about 12 to about 24 carbon atoms. Sorbitan is a mixture of sorbitans, primarily 1,4-sorbitan and isosorbide (Formulas I and II):
[0045]
[0046] Sorbitol anhydride (also referred to as monoanhydrosorbitol or sorbitan) is the common name for anhydrides derived from sorbitol by removing a water molecule. Sorbitol anhydride fatty acid esters of the present invention are mixtures of partial esters of sorbitol and its anhydride with fatty acids. These sorbitol anhydride esters can be represented by the following structure, which can be any one of monoesters, diesters, triesters, tetraesters or their mixtures (Formula III):
[0047]
[0048] In formula (III), each Z independently represents a hydrogen atom or C(O)R-, and each R independently represents a hydrocarbon group of about 9 to about 99 carbon atoms, more preferably about 11 to about 23 carbon atoms. Examples of sorbitan esters include sorbitan stearate and sorbitan oleate, such as sorbitan stearate (i.e., monostearate), sorbitan distearate, sorbitan tristearate, sorbitan monooleate, and sorbitan sesquioleate. Sorbitol esters also include polyoxyalkylene sorbitan esters, wherein the alkylene group has about 2 to about 30 carbon atoms. These polyoxyalkylene sorbitan esters can be represented by formula IV:
[0049]
[0050] wherein in Formula IV, each R is independently an alkylene group of from about 2 to about 30 carbon atoms; R' is a hydrocarbyl group of from about 9 to about 99 carbon atoms, more preferably from about 11 to about 23 carbon atoms; and w, x, y, and z represent the number of repeating oxyalkylene units. For example, ethoxylation of sorbitan fatty acid esters produces a series of more hydrophilic surfactants as a result of the reaction of the hydroxyl groups of sorbitan with ethylene oxide. A major class of these ethoxylated sorbitan esters are those containing from about 2 to about 80 ethylene oxide units, and in one embodiment from about 2 to about 30 ethylene oxide units, and in one embodiment about 4, in one embodiment about 5, and in one embodiment about 20 ethylene oxide units. Typical examples are polyoxyethylene (hereinafter referred to as "POE") (20) sorbitan tristearate, POE (4) sorbitan monostearate, POE (20) sorbitan trioleate, POE (5) sorbitan monooleate and POE (80) sorbitan monooleate. As used herein, the numbers in brackets refer to the number of ethylene oxide units present in the composition.
[0051] Useful surfactants of the types listed above can be generally represented by the following classes of chemical compounds, members of which are commercially available and suitable provided that their use in accordance with the teachings herein enables the production of stable emulsions:
[0052] (a) sorbitol esters, the general formula of which is
[0053]
[0054] Wherein: the groups X are identical or different from each other and are each OH or R 1 COO - ; where R 1 is a linear or branched, saturated or unsaturated aliphatic hydrocarbon group, which is optionally substituted by a hydroxyl group and has 7 to 22 carbon atoms, provided that at least one of the groups X is R 1 COO - ,
[0055] (b) fatty acid esters, the general formula of which is:
[0056]
[0057] Where: R 2 is a linear or branched, saturated or unsaturated aliphatic hydrocarbon group, which is optionally substituted by a hydroxyl group and has 7 to 22 carbon atoms; R 3 C is a straight chain or branched chain 1 -C 10 alkylene; n is an integer greater than or equal to 6; and R 4 H, straight or branched chain C 1 -C 10 Alkyl or
[0058]
[0059] Where R 5 As mentioned above, R 2 as defined; and
[0060] (c) polyalkoxylated alkylphenol, the general formula of which is
[0061]
[0062] Where: R 6 C is a straight chain or branched chain 1 -C 20 alkyl; m is an integer greater than or equal to 8; and
[0063] R 7 and R 8 As described above for R of formula (II), 3 and R 4 As defined.
[0064] Typically, the weight ratio of the sol to the oil and surfactant mixture can be from about 1:5 to about 5:1, such as from about 1:4 to about 4:1, such as from about 1:3 to about 2:1, such as from about 1:2 to about 2: 1. In some embodiments, the oil is mineral oil and the surfactant is a sorbitan ester, such as sorbitan monooleate, and the weight ratio ranges from 1:2 to 2:1.
[0065] To obtain the desired silica sol droplet size, the temperature can be controlled during the emulsion formation step. For example, the temperature can be maintained above about 30°C, such as about 40°C to about 80°C, such as about 50°C to about 65°C, when forming the emulsion.
[0066] The mixing speed should be high enough to form a stable emulsion, i.e., an emulsion that will not separate when placed at room temperature within the desired time period, and to obtain the desired silica sol droplet size. This mixing speed can be achieved using an overhead mixer (e.g., Dispermat mixing) or a pipeline mixer (e.g., Silverson mixer). After the sol is fully pumped into the reaction vessel or otherwise fully mixed, the emulsion can be continuously mixed for a period of time sufficient to maintain a stable emulsion. For example, in some embodiments, mixing can last for a period of time from about 1 minute to about 1 hour.
[0067] After forming the emulsion, the method proceeds to step 103, wherein the pH of the emulsion is optionally adjusted. The pH can be adjusted using an alkaline compound. For example, in various embodiments described herein, any known or later discovered base can be used to adjust the pH. In various embodiments, the base can be selected from NaOH, ammonia, ammonium hydroxide (e.g., NH 4 OH), KOH, Na 2 CO 3 , TMAOH (tetramethylammonium hydroxide), NaAlO 2and mixtures thereof. In addition, the alkali used can be in the form of a solution having a concentration range of 0.2% to 50%. In various embodiments, the above-mentioned alkali can have a pH of at least 7, such as about 8 to about 14, such as about 9 to about 13. The amount of the alkaline compound used is determined by the target pH to be achieved. For example, in some embodiments, the alkaline compound is added until the pH reaches a value of about 3 or greater, about 4 or greater in some embodiments, about 5 or greater in some embodiments, about 6 or greater in some embodiments, about 7 or greater in some embodiments, and about 8 or greater in some embodiments. The pH typically reaches about 12 or less, about 11 or less in some embodiments, about 10 or less in some embodiments, and about 9 or less in some embodiments. For example, in some embodiments, ammonium hydroxide is added until the pH reaches about 3 to about 10, such as about 5 to about 9. The emulsion can be continuously mixed when the alkaline compound is added, and thereafter for a period of time to promote pH stability. The mixing speed can be optionally reduced at this stage. For example, in some embodiments, the mixing speed is reduced to a speed of about 10% to about 60% of the mixing speed used to form the emulsion.
[0068] It should be understood that the pH does not necessarily need to be adjusted, and step 103 is optional. The pore characteristics of the resulting silica particles can be controlled by adjusting the pH of the emulsion during the gelation process. Therefore, the pH should be adjusted to the level required to obtain the desired pore characteristics. Therefore, in some cases, it is not necessary to adjust the pH at all.
[0069] After the optional pH adjustment step, the method can proceed to step 104, wherein the silica is gelled. The gelling process can include optionally adding water to the emulsion and raising the temperature, while optionally continuously mixing. The volume of water added at this stage is not critical, but can be about 0.25 times to about 10 times the volume of the mixture in the container. In other embodiments, no water is added.
[0070] The gelation temperature range may be from about 50°C to about 95°C, in some embodiments from about 75°C to about 85°C, for example, from about 75°C to about 85°C. The mixing speed may be maintained at a speed similar to that in step 103. The temperature and mixing speed may be maintained for a period of time sufficient to allow silica gelation. For example, in some embodiments, the gelation time may be from about 20 minutes to about 2 hours, for example, from about 30 minutes to about 90 minutes. In some embodiments, the obtained silica gel may be aged before separation, for example, by Ostwald ripening, wherein the obtained silica gel is maintained at a temperature of from about 50°C to about 95°C, in some embodiments from about 70°C to about 90°C, in some embodiments from about 75°C to about 85°C, for a period of from about 10 minutes to about 10 hours, in some embodiments from about 30 minutes to about 5 hours, in some embodiments from about 45 minutes to about 2 hours. The pH may optionally be adjusted during the aging process. In this way, the surface area and pore size may be adjusted in situ, and the gel network may be enhanced.
[0071] After the gelling step, the method can proceed to the separation in step 105. Any suitable method can be used to separate the solid silica gel particles from the oil phase and the water phase of the mixture. For example, in some embodiments, mixing is stopped so that the oil and surfactant are separated from the formed silica particles. In some embodiments, solid particles can be filtered out from the mixture.
[0072] The resulting silica particles may then be optionally washed in step 106, for example by stirring them in an acid, water, and / or alcohol. The particles may then be dried using any suitable method in step 107. For example, in some embodiments, the particles may be dried at a temperature and time sufficient to remove the desired amount of moisture. In some embodiments, the particles may be dried in a vacuum oven at a temperature of about 40° C. to about 80° C. for about 30 minutes to about 24 hours. In some embodiments, the particles may be dried in a conventional oven at a temperature of about 90° C. to about 130° C. for about 30 minutes to about 24 hours. In some embodiments, a spray dryer may be used to dry the particles. In other embodiments, the particles may be dried by flash drying or by co-evaporation using an organic solvent.
[0073] In some embodiments, in order to facilitate the separation of oil and surfactant from the emulsion, the emulsion is demulsified by adding a demulsifier. In some embodiments, the demulsifier is water or acid, such as an inorganic acid. For example, in some embodiments, deionized water or an aqueous inorganic acid is added to the emulsion as a demulsifier. For example, when using an aqueous sulfuric acid composition as a demulsifier, the concentration of sulfuric acid can be about 1 weight % to about 30 weight % of the total aqueous composition, and in some embodiments about 5 weight % to about 15 weight %. The demulsifier can be added to the emulsion in a weight ratio of about 1:5 to about 5:1 relative to the weight of the emulsion, and in some embodiments, in a weight ratio of about 1:2 to about 1:1.
[0074] Demulsification can occur at high temperatures. For example, the temperature can be from about 50°C to about 95°C, from about 60°C to about 90°C in some embodiments, and from about 70°C to about 80°C in some embodiments. During demulsification, the mixture can optionally be stirred by any suitable means. For example, in some embodiments, after adding a demulsifier, the mixture is stirred at high temperatures for about 30 minutes to about 5 hours, for example, from about 1 hour to about 3 hours. In other embodiments, the mixture is kept at high temperatures without stirring for about 30 minutes to about 5 hours, for example, from about 1 hour to about 3 hours.
[0075] After demulsification, the particles can be separated from the rest of the mixture by any suitable means. For example, in some embodiments, the mixture can be transferred to a separatory funnel to separate the aqueous phase from the oil phase. The silica particles can then be separated from the rest of the liquid. In some embodiments, for example, the particles can be repeatedly filtered and redispersed as needed.
[0076] After separation, optionally Figure 1 The particles are aged as shown in step 106a. The particles can be aged at high temperature in an ammonia solution. In some embodiments, the particles are redispersed in an aqueous medium, heated and mixed with ammonium hydroxide for an appropriate period of time. The pH of the redispersed particles in the aqueous medium can be from about 1 to about 5, for example, from about 2 to about 4. The aging temperature can be from about 50°C to about 95°C, in some embodiments from about 70°C to about 90°C, and in some embodiments from about 75°C to about 85°C. Ammonium hydroxide can be added until the pH of the solution reaches about 6 to about 9, for example, from about 7 to about 8. In some embodiments, the particles are aged for a period of about 10 minutes to about 10 hours, in some embodiments from about 30 minutes to about 5 hours, and in some embodiments from about 45 minutes to about 2 hours.
[0077] If the particles are aged in such a solution, they can then be filtered and dried. For example, in some embodiments, the particles can be filtered out of the ammonia solution, redispersed in water as needed, and then filtered and dried to remove water and any solvent to form a powder. In some embodiments, after filtering from the ammonia solution, the particles are redispersed in deionized water and then dried at high temperature for a suitable period of time. Any suitable temperature can be used to dry the particles. In some embodiments, for example, the particles are dried at a temperature of about 50°C to about 250°C, in some embodiments about 80°C to about 200°C, and in some embodiments about 100°C to about 150°C, for a period of about 1 hour to about 48 hours, for example, about 5 hours to about 24 hours.
[0078] Emulsion methods for forming silica particles can provide additional advantages over traditional silica supports. For example, in traditional spray-dried silica supports, the grinding process tends to produce very small silica particles, referred to as "fines." Even if the silica particles are highly sorted to remove fines, it is difficult to prevent some fines from remaining attached to the support particles and entering the polymerization reactor, causing static electricity and scaling, especially in gas phase reactors. However, advantageously, the silica supports of the present disclosure can have very low fines content because no grinding process is required when using the emulsion method. For example, in some embodiments, the number percentage of silica particles having a particle size of 1 μm or less is about 7% or less, in some embodiments about 4% or less, and in some embodiments about 2% to less than 1%.
[0079] During the above-mentioned method, silica gel particles are formed in droplets of emulsion to provide porous spherical silica particles. Each particle contains a rigid network of amorphous silica. Therefore, the particles tend to be highly spherical. One method of measuring the sphericity of particles is to take images of multiple particles and calculate the aspect ratio of each particle using the maximum diameter and minimum diameter of each particle that can be determined from the image. Then, the average aspect ratio of the particles can be calculated using the aspect ratio of a single particle. Therefore, particles with low aspect ratios are more spherical than particles with higher aspect ratios. In this regard, the particles formed by any of the above-mentioned methods are highly spherical and can have a low average aspect ratio, such as about 1.2 or less, about 1.17 or less in some embodiments, about 1.15 or less in some embodiments, about 1.12 or less in some embodiments, and about 1.1 or less in some embodiments. For example, in some embodiments, at least 75% of the particles have an aspect ratio of about 1.2 or less, such as about 1.1 or less. In some embodiments, at least 50% of the particles have an aspect ratio of about 1.1 or less. Typically the aspect ratio is 1.0 or greater.
[0080] Such high sphericity carrier particles can help produce polymer particles with good morphology and high bulk density. For example, the polyolefin particles produced using the catalyst system described herein can have a sedimentation bulk density greater than 0.4 g / cc. In addition, the average aspect ratio of the produced polyolefin particles can be less than about 1.2.
[0081] As mentioned above, the silica carrier can be used in a variety of catalyst forms. Ziegler-Natta, metallocene and chromium catalysts, co-catalysts and activator components can be impregnated in and on the carrier as described herein. For example, the catalyst component to be impregnated in the carrier can be dissolved or suspended in an organic solvent, the carrier is added thereto and slurried. The solvent can then be evaporated. The evaporation can be carried out in a conical dryer, which avoids applying high stress to the core material. Many variations on this theme are possible, and the specific impregnation technique will depend on the specific catalyst system to be adopted, as is well known in the art.
[0082] "Ziegler-Natta" catalysts are generally understood to include transition metal (IIIB to VIIIB) halides, alkyl compounds, aryl compounds or alkoxy compounds and mixtures thereof in combination with elements from Groups I to III of the Periodic Table. A typical example is TiCl 4 and AlEt 3 The preferred Ziegler-Natta system is one that employs a complex of magnesium chloride / titanium halide or alkoxide with an alkyl aluminum deposited on a silica support. Methods for producing the catalyst are known in the art. Electron donors that may also be used in the Ziegler-Natta catalyst system of the present invention include esters, ethers, amines, silanes and alcohols and mixtures thereof.
[0083] One suitable process for providing a silica supported Ziegler-Natta type catalyst is described in US Pat. No. 5,633,419, which is incorporated herein by reference.
[0084] For example, the Ziegler-Natta catalyst composition can include a magnesium halide, a transition metal compound, an alkyl aluminum co-catalyst, and an electron donor compound. These components can be incorporated into or supported on a silica support. For example, the catalyst components can be formed by impregnating a silica support with a magnesium halide solution or a solution of a magnesium-containing precursor that can be converted to a magnesium halide when halogenated.
[0085] The silica support can be impregnated by immersing the support particles in a solution of a magnesium halide (eg, magnesium chloride, magnesium bromide, magnesium iodide, and magnesium fluoride) dissolved in a polar solvent, stirring the solution for a sufficient period of time, and then removing the solvent.
[0086] Alternatively, the formula R 2-n MgX n.xMR' y The support is impregnated with a hydrocarbon-soluble magnesium compound wherein each R is independently a hydrocarbyl group having 1 to 20 carbon atoms, each X is independently a halogen or a hydrocarbyloxy group having 1 to 20 carbon atoms in its hydrocarbyl portion, n is 0 to 2, provided that if X is a halogen then n is at most 1, M is aluminum, zinc or boron, each R' is independently hydrogen, a hydrocarbyl group or a hydrocarbyloxy group having 1 to 20 carbon atoms in its hydrocarbyl portion, y has a value equal to the valence of M, and x has a value of 0 to 10. After impregnation of the silica support with the hydrocarbon-soluble magnesium compound, the magnesium halide can be formed by halogenation.
[0087] In some embodiments, the halogenating agent is selected from alkylaluminum halides, advantageously alkylaluminum sesquihalides or dihalides, hydrogen halides, silicon halides, and boron halides.
[0088] The transition metal compound may then be added to the supported magnesium halide component in any manner known in the art. The transition metal compound may be a Group 4 or Group 5 transition metal compound, such as a halide, alkoxide, or mixed halide / alkoxide of titanium, zirconium, hafnium, or vanadium. For example, a suitable Group 4 transition metal compound is represented by the formula MX 4-a (OR) a wherein M is titanium, zirconium or hafnium, each R is independently an alkyl group having 1 to about 20, preferably about 1 to about 10, more preferably 2 to about 8 carbon atoms; X is a halogen atom, preferably chlorine; and a has a value of 0 to 4. Suitable Group 5 transition metal compounds are preferably vanadium compounds, such as those of the formula VX 4 and V(O)X 3 A compound represented by wherein each X is independently OR or a halogen atom, preferably a chlorine atom, and each R is independently an alkyl group having 1 to about 20, preferably about 2 to about 8, more preferably about 2 to about 4 carbon atoms.
[0089] Various different types of internal electron donors may also be incorporated into the catalyst component in any suitable manner. In one embodiment, the internal electron donor is an aromatic diester, such as a phenylene-substituted diester. In one embodiment, the internal electron donor may have the following chemical structure:
[0090]
[0091] Where R 1 , R 2 , R 3 and R 4 Each is a hydrocarbon group having 1 to 20 carbon atoms, the hydrocarbon group having a branched or linear structure or containing a cycloalkyl group having 7 to 15 carbon atoms, wherein E 1 and E 2are the same or different and are selected from an alkyl group having 1 to 20 carbon atoms, a substituted alkyl group having 1 to 20 carbon atoms, an aryl group having 1 to 20 carbon atoms, a substituted aryl group having 1 to 20 carbon atoms or an inert functional group having 1 to 20 carbon atoms and optionally containing a heteroatom, and wherein X 1 and X 2 Each is O, S, an alkyl group or NR 5 , and where R 5 is a hydrocarbyl group having 1 to 20 carbon atoms or is hydrogen.
[0092] As used herein, the terms "hydrocarbyl" and "hydrocarbon" refer to substituents containing only hydrogen and carbon atoms, including branched or unbranched, saturated or unsaturated, cyclic, polycyclic, fused or acyclic species and combinations thereof. Non-limiting examples of hydrocarbyl groups include alkyl-, cycloalkyl-, alkenyl-, alkadienyl-, cycloalkenyl-, cycloalkadienyl-, aryl-, aralkyl, alkaryl and alkynyl- groups.
[0093] As used herein, the terms "substituted hydrocarbyl" and "substituted hydrocarbon" refer to hydrocarbyl groups substituted with one or more non-hydrocarbyl substituents. A non-limiting example of a non-hydrocarbyl substituent is a heteroatom. As used herein, "heteroatom" refers to an atom other than carbon or hydrogen. A heteroatom may be a non-carbon atom of Groups IV, V, VI, and VII of the Periodic Table of Elements. Non-limiting examples of heteroatoms include: halogens (F, Cl, Br, I), N, O, P, B, S, and Si. Substituted hydrocarbyl groups also include halogenated hydrocarbyl groups and silicon-containing hydrocarbyl groups. As used herein, the term "halogenated hydrocarbyl" group refers to a hydrocarbyl group substituted with one or more halogen atoms. As used herein, the term "silicon-containing hydrocarbyl group" is a hydrocarbyl group substituted with one or more silicon atoms. The silicon atom(s) may or may not be in the carbon chain.
[0094] In one aspect, the substituted phenylene diester has the following structure (I):
[0095]
[0096] In one embodiment, R in structure (I) 1 and R 3 is isopropyl. 2 , R 4 and R 5 -R 14 Each is hydrogen.
[0097] In one embodiment, R in structure (I) 1 , R 5 and R 10 Each is a methyl group, R 3 R is tert-butyl.2 , R 4 , R 6 -R 9 and R 11 -R 14 Each is hydrogen.
[0098] In one embodiment, R in structure (I) 1 , R 7 and R 12 Each is a methyl group, R 3 R is tert-butyl. 2 , R 4 , R 5 , R 6 , R 8 , R 9 , R 10 , R 11 , R 13 and R 14 Each is hydrogen.
[0099] In one embodiment, R in structure (I) 1 is methyl, R 3 R is tert-butyl. 7 and R 12 Each is ethyl. 2 , R 4 , R 5 , R 6 , R 8 , R 9 , R 10 , R 11 , R 13 and R 14 Each is hydrogen.
[0100] In one embodiment, R in structure (I) 1 , R 5 , R 7 , R 9 , R 10 , R 12 and R 14 Each is a methyl group, R 3 R is tert-butyl. 2 , R 4 , R 6 , R 8 , R 11 and R 13 Each is hydrogen.
[0101] In one embodiment, R in structure (I) 1 is methyl, R 3 R is tert-butyl. 5 , R 7 , R9 , R 10 , R 12 and R 14 Each is isopropyl. 2 , R 4 , R 6 , R 8 , R 11 and R 13 Each is hydrogen.
[0102] In one embodiment, the substituted phenylene aromatic diester has a structure selected from structures (II)-(V), including R 1 To R 14 Alternative forms of each are described in detail in US Pat. No. 8,536,372, which is incorporated herein by reference.
[0103] In one embodiment, R in structure (I) 1 is methyl, R 3 R is tert-butyl. 7 and R 12 Each is an ethoxy group. 2 , R 4 , R 5 , R 6 , R 8 , R 9 , R 10 , R 11 , R 13 and R 14 Each is hydrogen.
[0104] In one embodiment, R in structure (I) 1 is methyl, R 3 R is tert-butyl. 7 and R 12 Each is a fluorine atom. 2 , R 4 , R 5 , R 6 , R 8 , R 9 , R 10 , R 11 , R 13 and R 14 Each is hydrogen.
[0105] In one embodiment, R in structure (I) 1 is methyl, R 3 R is tert-butyl. 7 and R 12 Each is a chlorine atom. 2 , R 4 , R 5 , R6 , R 8 , R 9 , R 10 , R 11 , R 13 and R 14 Each is hydrogen.
[0106] In one embodiment, R in structure (I) 1 is methyl, R 3 R is tert-butyl. 7 and R 12 Each is a bromine atom. 2 , R 4 , R 5 , R 6 , R 8 , R 9 , R 10 , R 11 , R 13 and R 14 Each is hydrogen.
[0107] In one embodiment, R in structure (I) 1 is methyl, R 3 R is tert-butyl. 7 and R 12 Each is an iodine atom. 2 , R 4 , R 5 , R 6 , R 8 , R 9 , R 10 , R 11 , R 13 and R 14 Each is hydrogen.
[0108] In one embodiment, R in structure (I) 1 is methyl, R 3 R is tert-butyl. 6 , R 7 , R 11 and R 12 Each is a chlorine atom. 2 , R 4 , R 5 , R 8 , R 9 , R 10 , R 13 and R 14 Each is hydrogen.
[0109] In one embodiment, R in structure (I) 1 is methyl, R 3 R is tert-butyl.6 , R 8 , R 11 and R 13 Each is a chlorine atom. 2 , R 4 , R 5 , R 7 , R 9 , R 10 , R 12 and R 14 Each is hydrogen.
[0110] In one embodiment, R in structure (I) 1 is methyl, R 3 R is tert-butyl. 2 , R 4 and R 5 -R 14 Each is a fluorine atom.
[0111] In one embodiment, R in structure (I) 1 is methyl, R 3 R is tert-butyl. 7 and R 12 Each is trifluoromethyl. 2 , R 4 , R 5 , R 6 , R 8 , R 9 , R 10 , R 11 , R 13 and R 14 Each is hydrogen.
[0112] In one embodiment, R in structure (I) 1 is methyl, R 3 R is tert-butyl. 7 and R 12 Each is an ethoxycarbonyl group. 2 , R 4 , R 5 , R 6 , R 8 , R 9 , R 10 , R 11 , R 13 and R 14 Each is hydrogen.
[0113] In one embodiment, R 1 is methyl, R 3 R is tert-butyl. 7 and R 12 Each is an ethoxy group. 2 , R4 , R 5 , R 6 , R 8 , R 9 , R 10 , R 11 , R 13 and R 14 Each is hydrogen.
[0114] In one embodiment, R in structure (I) 1 is methyl, R 3 R is tert-butyl. 7 and R 12 Each is diethylamino. 2 , R 4 , R 5 , R 6 , R 8 , R 9 , R 10 , R 11 , R 13 and R 14 Each is hydrogen.
[0115] In one embodiment, R in structure (I) 1 is methyl, R 3 It is 2,4,4-trimethylpentan-2-yl. 2 , R 4 and R 5 -R 14 Each is hydrogen.
[0116] In one embodiment, R in structure (I) 1 and R 3 Each is a sec-butyl group. 2 , R 4 and R 5 -R 14 Each is hydrogen.
[0117] In one embodiment, R in structure (I) 1 and R 4 Each is a methyl group. 2 , R 3 , R 5 -R 9 and R 10 -R 14 Each is hydrogen.
[0118] In one embodiment, R in structure (I) 1 R is methyl. 4 is isopropyl. 2 , R 3 , R 5 -R9 and R 10 -R 14 Each is hydrogen.
[0119] In one embodiment, R in structure (I) 1 , R 3 and R 4 Each is isopropyl. 2 , R 5 -R 9 and R 10 -R 14 Each is hydrogen.
[0120] In another aspect, the internal electron donor can be a phthalate compound. For example, the phthalate compound can be dimethyl phthalate, diethyl phthalate, dipropyl phthalate, diisopropyl phthalate, dibutyl phthalate, diisobutyl phthalate, dipentyl phthalate, diisopentyl phthalate, methyl butyl phthalate, ethyl butyl phthalate, or ethyl propyl phthalate.
[0121] In addition to the above catalyst components, the Ziegler-Natta catalyst system of the present disclosure may also include a co-catalyst. The co-catalyst may include hydrides, alkylates or arylates of aluminum, lithium, zinc, tin, cadmium, beryllium, magnesium, and combinations thereof. In one embodiment, the co-catalyst is a hydrocarbyl aluminum co-catalyst having a formula R 3 A1 represents, wherein each R is an alkyl, cycloalkyl, aryl or hydride group; at least one R is a hydrocarbyl group; two or three R groups can be connected to a cyclic group to form a heterocyclic structure; each R can be the same or different; and each R (which is a hydrocarbyl group) has 1 to 20 carbon atoms, preferably 1 to 10 carbon atoms. In a further embodiment, each alkyl group can be linear or branched, and this hydrocarbyl group can be a mixed group, that is, the group can include alkyl, aryl and / or cycloalkyl. Non-limiting examples of suitable groups are: methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, neopentyl, n-hexyl, 2-methylpentyl, n-heptyl, n-octyl, isooctyl, 2-ethylhexyl, 5,5-dimethylhexyl, n-nonyl, n-decyl, isodecyl, n-undecyl and n-dodecyl.
[0122] Non-limiting examples of suitable hydrocarbyl aluminum compounds are as follows: triisobutylaluminum, tri-n-hexylaluminum, diisobutylaluminum hydride, di-n-hexylaluminum hydride, isobutylaluminum dihydride, n-hexylaluminum dihydride, diisobutylhexylaluminum, isobutyldihexylaluminum, trimethylaluminum, triethylaluminum, tri-n-propylaluminum, triisopropylaluminum, tri-n-butylaluminum, tri-n-octylaluminum, tri-n-decylaluminum, tri-n-dodecylaluminum. In one embodiment, the cocatalyst is selected from triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, diisobutylaluminum hydride and di-n-hexylaluminum hydride.
[0123] Alternatively, the olefin polymerization catalyst system can include a catalyst precursor compound, such as a metallocene component, and an activator supported on a silica support. The metallocene catalyst can include "semi-sandwich" and "full-sandwich" compounds having one or more Cp ligands (cyclopentadienyl ligands and ligands isolobal to cyclopentadienyl) bonded to at least one Group 3 to Group 12 metal atom and one or more leaving groups bonded to at least one metal atom.
[0124] The Cp ligand is one or more rings or (one or more) ring systems, at least a portion of which includes a π-bonded system, such as cyclodienyl ligands and heterocyclic analogs. The (one or more) rings or (one or more) ring systems typically contain atoms selected from Groups 13 to 16 atoms, and in some embodiments, the atoms constituting the Cp ligand are selected from carbon, nitrogen, oxygen, silicon, sulfur, phosphorus, germanium, boron, aluminum, and combinations thereof, wherein carbon constitutes at least 50% of the ring members. For example, the (one or more) Cp ligands can be selected from substituted and unsubstituted cyclopentadienyl ligands and ligands isomorphous to cyclopentadienyl. Non-limiting examples of such ligands include cyclopentadienyl, cyclopentaphenanthryl, indenyl, benzoindenyl, fluorenyl, octahydrofluorenyl, cyclooctatetraenyl, cyclopentacyclododecene, phenanthroindenyl, 3,4-benzofluorenyl, 9-phenylfluorenyl, 8-H-cyclopenta[a]acenaphthene, 7-H-dibenzofluorenyl, indeno[1,2-9]anthrene, thienoindenyl, thienofluorenyl, hydrogenated forms thereof (e.g., 4,5,6,7-tetrahydroindenyl or "H"); 4 Ind"), substituted forms thereof (as discussed and described in more detail below), and heterocyclic forms thereof.
[0125] The metal atom "M" of the metallocene compound can be selected from atoms of Groups 3 to 12 and lanthanide atoms; or can be selected from atoms of Groups 3 to 10; or can be selected from Sc, Ti, Zr, Hf, V, Nb, Ta, Mn, Re, Fe, Ru, Os, Co, Rh, Ir and Ni; or can be selected from atoms of Groups 4, 5, and 6; or can be Ti, Zr, or Hf atoms; or can be Hf; or can be Zr. The oxidation state of the metal atom "M" can be 0 to +7; or can be +1, +2, +3, +4 or +5; or can be +2, +3 or +4. The group bonded to the metal atom "M" makes the compounds and structures described in the structures below electrically neutral unless otherwise stated. (One or more) Cp ligands form at least one chemical bond with the metal atom M to form a "metallocene catalyst component". The difference between the Cp ligand and the leaving group bonded to the metal atom M is that they are very resistant to substitution / abstraction reactions.
[0126] In one embodiment, the metallocene catalyst may be represented by the formula:
[0127] (C 5 R x )yR′ z (C 5 R m )MQ n-y-1
[0128] Wherein, M is a metal from Group IIIB to Group VIII of the Periodic Table; (C 5 R x ) and (C 5 R m ) are the same or different cyclopentadienyl or substituted cyclopentadienyl groups bonded to M; R are the same or different and are hydrogen or a hydrocarbon group, such as an alkyl, alkenyl, aryl, alkaryl or aralkyl group, which contains 1 to 20 carbon atoms or two carbon atoms joined together to form a C 4 -C 6 Ring; R' is C 1 -C 4 A substituted or unsubstituted alkylene group, a dialkyl or diaryl germanium or silicon, or a bridged group of two (C 5 R x ) and (C 5 R m) ring; Q is a hydrocarbon radical having 1 to 20 carbon atoms (e.g., an aryl, alkyl, alkenyl, alkaryl or aralkyl radical), a hydrocarboxy radical having 1 to 20 carbon atoms, or a halogen, and may be the same as or different from each other; z is 0 or 1; y is 0, 1 or 2; when y is 0, z is 0; n is 0, 1, 2, 3 or 4, depending on the valence state of M; and ny≧1.
[0129] Illustrative but non-limiting examples of the metallocenes represented by the above formula are dialkyl metallocenes such as bis(cyclopentadienyl)dimethyltitanium, bis(cyclopentadienyl)diphenyltitanium, bis(cyclopentadienyl)dimethylzirconium, bis(cyclopentadienyl)diphenylzirconium, bis(cyclopentadienyl)dimethylhafnium and bis(cyclopentadienyl)diphenylhafnium, bis(cyclopentadienyl)dineopentyltitanium, bis(cyclopentadienyl)dineopentylzirconium, bis(cyclopentadienyl)dibenzyltitanium, bis(cyclopentadienyl)dibenzylzirconium, bis(cyclopentadienyl)dimethylvanadium; monoalkyl metallocenes such as bis(cyclopentadienyl)methyltitanium chloride, bis(cyclopentadienyl)ethyltitanium chloride, bis(cyclopentadienyl)dimethyltitanium, bis(cyclopentadienyl)diphenylzirconium, bis(cyclopentadienyl)dimethylhafnium and bis(cyclopentadienyl)diphenylhafnium; cyclopentadienyl)phenyl titanium chloride, bis(cyclopentadienyl)methyl zirconium chloride, bis(cyclopentadienyl)ethyl zirconium chloride, bis(cyclopentadienyl)phenyl zirconium chloride, bis(cyclopentadienyl)methyl titanium bromide; trialkyl metallocenes, such as cyclopentadienyl trimethyl titanium, cyclopentadienyl triphenyl zirconium, cyclopentadienyl trineopentyl zirconium, cyclopentadienyl trimethyl zirconium, cyclopentadienyl triphenyl hafnium, cyclopentadienyl trineopentyl hafnium, cyclopentadienyl trimethyl hafnium; monocyclopentadienyl titanocenes, such as pentamethyl cyclopentadienyl titanium trichloride, pentaethyl cyclopentadienyl titanium trichloride; bis(pentamethyl cyclopentadienyl) diphenyl titanium, bis(cyclopentadienyl) titanium of the formula =CH 2substituted bis(cyclopentadienyl)titanium(IV) compounds, for example: bis(indenyl)diphenyltitanium or bis(indenyl)titanium dichloride, bis(methylcyclopentadienyl)diphenyltitanium or bis(methylcyclopentadienyl)titanium dihalide; dialkyl, trialkyl, tetraalkyl and pentaalkylcyclopentadienyltitanium compounds, for example bis(1,2-dimethylcyclopentadienyl)diphenyltitanium or bis(1,2-dimethylcyclopentadienyl)titanium dichloride, bis(1,2-diethylcyclopentadienyl)diphenyltitanium or bis(1,2-diethylcyclopentadienyl)titanium dichloride; silicon-, phosphine-, amine- or carbon-bridged cyclopentadiene complexes, for example dimethylsilyldicyclopentadienyldiphenyltitanium or dimethylsilane dichloromethyl bis(cyclopentadienyl) titanium, bis(cyclopentadienyl) titanium dichloride ... Zirconium, diisopropylmethylene (2,5-dimethylcyclopentadienyl) (fluorenyl) zirconium dichloride, isopropyl (cyclopentadienyl) (fluorenyl) hafnium dichloride, diphenylmethylene (cyclopentadienyl) (fluorenyl) hafnium dichloride, diisopropylmethylene (cyclopentadienyl) (fluorenyl) hafnium dichloride, diisobutylmethylene (cyclopentadienyl) (fluorenyl) hafnium dichloride, di-tert-butylmethylene (cyclopentadienyl) (fluorenyl) hafnium dichloride, cyclohexylene (cyclopentadienyl) (fluorenyl) hafnium dichloride, diisopropylmethylene (2,5-dimethylcyclopentadienyl) (fluorenyl) hafnium dichloride, isopropyl (cyclopentadienyl) (fluorenyl) titanium dichloride, diphenylmethylene (cyclopentadienyl) (fluorenyl) titanium dichloride, diisopropylmethylene ( Cyclopentadienyl)(fluorenyl)titanium dichloride, diisobutylmethylene(cyclopentadienyl)(fluorenyl)titanium dichloride, di-tert-butylmethylene(cyclopentadienyl)(fluorenyl)titanium dichloride, cyclohexyl(cyclopentadienyl)(fluorenyl)titanium dichloride, diisopropylmethylene(2,5-dimethylcyclopentadienylfluorenyl)titanium dichloride, racemic-ethylenebis(1-indenyl)zirconium(IV) dichloride, racemic-ethylenebis(4,5,6,7-tetrahydro-1-indenyl)zirconium(IV) dichloride, racemic-dimethylsilylbis(1-indenyl)zirconium(IV) dichloride, racemic-dimethylsilylbis(4,5,6,7-tetrahydro-1-indenyl)zirconium(IV) dichloride, racemic-1,1,2,2-Tetramethylsilanylenebis(1-indenyl)zirconium(IV) dichloride, racemic-1,1,2,2-tetramethylsilanylenebis(4,5,6,7-tetrahydro-1-indenyl)zirconium(IV) dichloride, ethylene(1-indenyltetramethylcyclopentadienyl)zirconium(IV) dichloride, racemic-dimethylsilylbis(2-methyl-4-tert-butyl-1-cyclopentadienyl)zirconium(IV) dichloride, racemic-ethylenebis(1-indenyltetramethylcyclopentadienyl)zirconium(IV) dichloride (1-indenyl) hafnium (IV) dichloride, racemic-ethylenebis (4,5,6,7-tetrahydro-1-indenyl) hafnium (IV) dichloride, racemic-dimethylsilylbis (1-indenyl) hafnium (IV) dichloride, racemic-dimethylsilylbis (4,5,6,7-tetrahydro-1-indenyl) hafnium (IV) dichloride, racemic-1,1,2,2-tetramethylsilylbis (1-indenyl) hafnium (IV) dichloride, racemic-1,1,2 ,2-Tetramethylsilylenebis(4,5,6,7-tetrahydro-1-indenyl)hafnium(IV)dichloride,ethylene(1-indenyl-2,3,4,5-tetramethyl-1-cyclopentadienyl)hafnium(IV)dichloride,racemic-ethylenebis(1-indenyl)titanium(IV)dichloride,racemic-ethylenebis(4,5,6,7-tetrahydro-1-indenyl)titanium(IV)dichloride,racemic-dimethylsilylbis(1-indenyl)titanium(IV)dichloride , racemic-dimethylsilylbis(4,5,6,7-tetrahydro-1-indenyl)titanium(IV) dichloride, racemic-1,1,2,2-tetramethylsilylenebis(1-indenyl)titanium(IV) dichloride, racemic-1,1,2,2-tetramethylsilylenebis(4,5,6,7-tetrahydro-1-indenyl)titanium(IV) dichloride and ethylidene(1-indenyl-2,3,4,5-tetramethyl-1-cyclopentadienyl)titanium(IV) dichloride.
[0130] Activators can also be used with metallocene catalysts. The activator can be, for example, an aluminoxane, a borane, or a borate / ester compound. Useful activators include activators having the following general formula:
[0131] M 3 M 4 v X 2 c R 3 b-c
[0132] Among them, M 3 A metal of Group IA, Group IIA and Group IIIA of the Periodic Table of Elements; M 4 is a metal of Group IA of the periodic table; v is a number from 0 to 1; each X 2 is any halogen; c is a number from 0 to 3; each R 3is a monovalent hydrocarbon group or hydrogen; b is a number from 1 to 4; wherein bc is at least 1.
[0133] Compounds having only one Group IA, Group IIA or Group IIIA metal suitable for use in the practice of this invention include compounds having the formula:
[0134] M 3 R 3 k
[0135] Where: M 3 is a metal of Group IA, Group IIA or Group IIIA, such as lithium, sodium, beryllium, barium, boron, aluminum, zinc, cadmium and gallium; k is equal to 1, 2 or 3, depending on M 3 The valence of the compound usually depends on M 3 to a particular group (i.e., Group IA, Group IIA, or Group IIIA); and each R 3 It can be any monovalent hydrocarbon group. 3 Examples of groups include any of the above R 3 In some embodiments, the activator is selected from methylaluminoxane, tris-perfluorophenyl borate, and trityl tetra-perfluorophenyl borate.
[0136] Advantageously, the silica supports described herein can accommodate relatively high activator loadings. For example, in some embodiments, the organoaluminum compound is loaded on the support such that the catalyst system contains about 10 wt % or more Al. Typically, the Al loading is about 25 wt % or less.
[0137] The olefin polymerization catalyst system may also include a chromium compound supported by or incorporated into a silica support. More specifically, the chromium catalyst may be prepared by contacting the silica support with a chromium compound (e.g., a salt) that is at least partially soluble in water or an organic liquid medium. In some embodiments, an aqueous solution or suspension of the chromium salt may be contacted with an aqueous slurry of the support particles.
[0138] Chromium compounds suitable for forming the subject catalyst composition may be selected from chromium salts of any inorganic or organic acid which have a degree of solubility in the medium used to mix the salt with the silica, if applicable. The preferred medium is water. For example, suitable inorganic salts are chromium halides, such as chromium dichloride, chromium chloride hexahydrate, chromium dibromide, chromium bromide hexahydrate, chromium tribromide, chromium difluoride; and chromium nitrate; chromic anhydride, chromium phosphate; chromium sulfate (II); chromium sulfate pentahydrate and chromium sulfate octahydrate; chromium orthophosphate, etc. and mixtures thereof.
[0139] Organic chromium compounds suitable as a source of chromium atoms for forming the catalyst of the present invention include organic acid salts, such as chromium acetate, chromium acetate hydrate, chromium acetylacetonate, chromium propionate, chromium oxalate hydrate, chromium oxalate hexahydrate; amine complexes, such as hexaamine chromium (III) chloride; chloropentamine chromium chloride; hexaurea chromium (III) fluorosilicate; chromocene, etc. and mixtures thereof.
[0140] It has been found that certain chromium compounds useful herein have greater solubility in organic solvents. These compounds include, for example, chromocene, bis-(triphenylsilyl)chromate, and the like. In this case, the salt can be contacted with the support using an organic liquid solution, and the organic solvent can then be evaporated under vacuum at a temperature from ambient temperature to about 40°C.
[0141] In some embodiments, the chromium precursor includes chromium sulfate, chromium nitrate, chromium acetate, and chromium acetylacetonate.
[0142] The chromium precursor may be fixed to the support by contacting the support with a chromium precursor salt solution.
[0143] In various cases, the chromium precursor is introduced as an aqueous or organic solution or slurry. The materials may be contacted for a period of time of from about 15 minutes to about 150 minutes, preferably from about 15 minutes to 100 minutes. In some cases, the materials are mixed for 15 minutes to 60 minutes and then allowed to remain in the mixer without agitation for a period of time of up to about 180 minutes. The materials are typically mixed at a temperature of from ambient temperature to about 40°C.
[0144] The resulting supported chromium catalyst is then dried. The support product treated with a chromium precursor is oxidized to oxidize the chromium atoms to chromium (VI) oxide. The oxidation is usually carried out at a sufficient temperature and time to reduce the total volatiles to about 0.1% by weight to 8% by weight, wherein the total volatiles are determined by measuring the weight loss when the sample is destructively calcined at 1000°C. However, the oxidation is usually carried out by heating the support treated with the chromium precursor to a temperature of usually about 600°F to about 1800°F (157°C to 815°C), preferably about 800°F to about 1600°F, and most preferably about 800°F to about 1300°F, for a period of usually about 1 minute to about 600 minutes (e.g., 50 minutes to 600 minutes), preferably about 50 minutes to about 300 minutes. The oxidizing atmosphere should be dry air or other oxygen-containing gases. The oxidation should be carried out in a manner to avoid sintering.
[0145] The catalyst system can be used to produce various polyolefins by contacting olefin monomers with a catalyst system comprising a silica support and any of the catalyst precursor compounds described above. The polymerization process can be a bulk polymerization process, a solution phase process, a slurry phase process, or a gas phase process.
[0146] In a slurry olefin polymerization process, the silica support typically has a median particle size of about 5 μm to about 100 μm, such as about 20 μm to about 80 μm.
[0147] In a gas phase olefin polymerization process, the silica support preferably has a median particle size of about 20 μm or greater, such as about 30 μm or greater, such as about 50 μm to about 100 μm.
[0148] In solution and high pressure olefin polymerization processes, the silica support preferably has a median particle size of about 4 μm to about 40 μm, such as about 5 μm to about 30 μm, for example about 6 μm to about 20 μm.
[0149] Suitable olefins that can be polymerized in contact with the catalyst composition of the present invention include, for example, alpha-olefins having 2 to about 20, preferably about 2 to about 12, more preferably about 2 to about 8 carbon atoms and a combination of two or more such alpha-olefins. Particularly suitable alpha-olefins include, for example, ethylene, propylene, 1-butene, 1-pentene, 4-methylpentene-1, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene or a combination thereof. Preferably, the alpha-olefin is a combination of ethylene, propylene, 1-butene, 4-methylpentene-1, 1-hexene, 1-octene, and ethylene and / or propylene with one or more such other alpha-olefins.
[0150] The slurry process generally uses an inert hydrocarbon diluent and a temperature of about 0°C to just below the temperature at which the resulting polymer becomes substantially soluble in the inert polymerization medium. The preferred temperature is about 60°C to about 105°C. The pressure range is generally 1 bar to 100 bar. The solution process is carried out at a temperature of about 275°C at which the resulting polymer is soluble in the inert solvent or the specific monomer, preferably at a temperature of about 130°C to about 260°C, more preferably about 150°C to about 240°C. As an inert solvent, hydrocarbons, preferably aliphatic hydrocarbons, are generally used. In the solution process, the pressure is generally 1 bar to 100 bar. Typical operating conditions for gas phase polymerization are 20°C to 100°C, more preferably 40°C to 80°C. In the gas phase process, the pressure is generally negative pressure to 100 bar. The high pressure process is carried out at a temperature of about 100°C to about 400°C and at a pressure of 500 bar to 3000 bar.
[0151] The invention thus summarized will be more readily understood by reference to the following examples which are provided for illustration only and are not intended to be limiting of the invention.
[0152] Example
[0153] Test method:
[0154] Surface area, pore volume and average pore size were measured by nitrogen adsorption. The instrument used for the analysis was an autosorb iQ2 TPX from Quantachrome Instrument. The nitrogen adsorption method is known as BET and is described in S. Brunauer, PH Emmett and E. Teller, J. Am. Chem. Soc., 1938, 60, 309.
[0155] Prior to analysis, the samples were vacuum activated at 400°C for 30 minutes. The surface area was calculated from multiple points of nitrogen volume uptake during the adsorption branch at low [P / Po = ~0.05 to 0.15] partial pressures. The adsorption branch of the isotherm was stopped at a partial pressure of P / Po = 0.995, and the descending branch of the isotherm was then measured. The pore volume was calculated by applying the Gurvich rule at P / Po = 0.995. The pore size is reported as the calculated BJH desorption average diameter.
[0156] The silica gels of the present invention are typical mesoporous materials (pore size 2-50 nm, IUPAC definition), and they generally show type IV isotherms (IUPAC classification). Therefore, nitrogen porosimetry is a suitable method for characterizing them, and the determination of surface area using the BET method and the determination of pore volume from nitrogen adsorption and desorption isotherms using the BJH method are well-established and suitable methods and are used herein.
[0157] After 2 minutes of ultrasonic treatment, the median particle size (D50) and the particle size distribution were measured using a Malvern MS3000 particle size analyzer apparatus from Brightwell Technologies Inc. The refractive index used in the measurements was 1.49.
[0158] The aspect ratio was determined from the SEM micrographs using Image-Pro Premier software. For each particle in the sample image, the aspect ratio was calculated by dividing the longest diameter by the shortest diameter. The aspect ratios of the individual particles of each sample were then averaged to determine the average aspect ratio of the particles in the sample. For each sample for which an aspect ratio was provided, approximately 150 particles were used for the calculation.
[0159] Melt flow rate is measured according to ISO 1133-1:2011 (technically equivalent to ASTM D1238-13) at a load of 2.16 kg and a temperature of 190°C.
[0160] Example 1
[0161] Use emulsion method to obtain porous spherical silica material. First, sodium silicate and inorganic acid are reacted to prepare sol. Sol is prepared at a temperature of 15°C and a pH of 1.5 by adding 200g sodium silicate (14 wt %) to 53g acid (18.5% HCl) at a flow rate of 10ml / min and mixing at 960rpm using an overhead mixer for 20 minutes. Then the sol is pumped into a mixture of mineral oil (300g) and a surfactant (sorbitan monooleate, 15g). The mixture is continuously mixed for 10 minutes at a speed of 960rpm using an overhead mixer at a temperature (60°C) to prepare an emulsion. pH is adjusted to control the gelation process by adding 2.9g ammonium hydroxide to the emulsion. The emulsion is then mixed at 250rpm for 5 minutes. 400ml water is added to the emulsion. The temperature is then raised to 80°C. The emulsion is mixed at 250rpm for 1 hour to gel. After gelation, the mixture was cooled for 30 minutes to separate the oil phase from the aqueous phase. The aqueous phase containing the silica particles was collected and the silica particles were filtered out from the aqueous phase. The silica particles were washed with 200 ml of water at pH 4 at 60°C while mixing at 250 rpm for 40 minutes and then filtered. The washing step was repeated twice more. The particles were then washed with isopropanol and subsequently dried in a vacuum oven at 60°C for 1 hour. The resulting particles were spherical porous silica with a D50 particle size of 14 μm and a span of 1.5. The BET surface area of the resulting particles was 456 m 2 / g, pore volume 1.5ml / g, average pore diameter about Figure 4 An image of the particle is shown. Figure 2 An image of the particle is shown.
[0162] Example 2
[0163] Use emulsion method to obtain porous spherical silica material. First, sodium silicate and inorganic acid are reacted to prepare sol. Sol is prepared at a temperature of 15°C and a pH of 1.5 by adding 253g sodium silicate (14 wt %) to 50.5g acid (18.5% HCl) at a flow rate of 10ml / min and mixing at 960rpm using an overhead mixer for 20 minutes. Then the sol is pumped into a mixture of oil (150g) and a surfactant (sorbitan monooleate, 10g). The mixture is continuously mixed for 10 minutes at a speed of 960rpm using an overhead mixer at a stable temperature (60°C) to prepare an emulsion. pH is adjusted to control the gelation process by adding 2.4g ammonium hydroxide to the emulsion. The emulsion is then mixed at 250rpm for 5 minutes. 400ml water is added to the emulsion. The temperature is then raised to 80°C. The emulsion is mixed at 250rpm for 1 hour to gel. After gelation, the mixture was cooled for 30 minutes to separate the oil phase from the aqueous phase. The aqueous phase containing the silica particles was collected and the silica particles were filtered out from the aqueous phase. The silica particles were washed with 200 ml of water at pH 4 at 60°C while mixing at 250 rpm for 40 minutes and then filtered. The washing step was repeated twice more. The particles were then washed with isopropanol and subsequently dried in a vacuum oven at 60°C for 1 hour. The resulting particles were spherical porous silica with a D50 particle size of 17 μm and a span of 1.3. The BET surface area of the resulting particles was 917 m 2 / g, pore volume 1.9ml / g, average pore diameter about Figure 3 An image of the particle is shown.
[0164] Example 3
[0165] Use emulsion method to obtain porous spherical silica material. First, sodium silicate and inorganic acid are reacted to prepare sol. Sol is prepared at a temperature of 15°C and a pH of 1.5 by adding 201g sodium silicate (14 wt %) to 53.5g acid (18.5% HCl) at a flow rate of 10ml / min and mixing at 960rpm using an overhead mixer for 20 minutes. Then the sol is pumped into a mixture of oil (91g) and a surfactant (sorbitan monooleate, 7.7g). The mixture is continuously mixed for 10 minutes at a speed of 960rpm using an overhead mixer at a stable temperature (60°C) to prepare an emulsion. pH is adjusted to control the gelation process by adding 1.0g ammonium hydroxide to the emulsion. The emulsion is mixed for another 5 minutes at 250rpm. 400ml water is added to the emulsion. The temperature is then raised to 80°C. The emulsion is mixed at 250rpm for 1 hour to gel. After gelation, the mixture was cooled for 30 minutes to separate the oil phase from the aqueous phase. The aqueous phase containing the silica particles was collected and the silica particles were filtered out from the aqueous phase. The silica particles were washed with 200 ml of water at pH 4 at 60°C while mixing at 250 rpm for 40 minutes and then filtered. The washing step was repeated twice more. The particles were then washed with isopropanol and subsequently dried in a vacuum oven at 60°C for 1 hour. The resulting particles were spherical porous silica with a D50 particle size of 9 μm and a span of 1.1. The BET surface area of the resulting particles was 505 m 2 / g, pore volume 2.5ml / g, average pore diameter about Figure 4 An image of the particle is shown.
[0166] Table 1 summarizes the properties of the silica particles produced in Examples 1-3.
[0167] Table 1
[0168]
[0169]
[0170] Example 4
[0171] The mesoporous silica material was obtained using an emulsion method. First, sodium silicate and acid were reacted to prepare a sol, and then the sol was added to oil and a surfactant to generate an emulsion. Sodium silicate (18%) was added to an acid (50.0 g, 42% H 2 SO 4The sol was prepared by mixing the mixture of mineral oil (CX) and surfactant (sorbitan monooleate) at 500 rpm for 30 minutes at a controlled temperature (≤25°C) and pH (≤1.5). The sol was then pumped into a mixed mineral oil (CX) and surfactant (sorbitan monooleate). After the sol was completely pumped in, it was continuously mixed (using a Rushton impeller) at a speed of 400 rpm for 25 minutes at ambient temperature to prepare an emulsion. The pH was adjusted by adding 6.0 g of ammonium hydroxide to the emulsion over 2 minutes to control the gelation process of the sol. The mixing was continued for another 5 minutes at a speed reduced to 250 rpm. Without stirring, the temperature was raised to 80°C and the emulsion was left to stand for 1 hour. After reacting for 1 hour, 400 ml of 10% sulfuric acid was added at a speed of 250 rpm for 1 hour, and the temperature was kept at 80°C. Then, the mixture was placed for 30 minutes to cool, so that the oil and surfactant were separated from the resulting silica particles. The mixture was then filtered to separate the oil and surfactant from the silica particles. The silica particles were then washed with 250 ml of 80°C water while mixing at 250 rpm for 30 minutes and then filtered. The washing step was repeated two more times. The particles were then washed once with isopropanol and the sample was subsequently dried in a vacuum oven at 60°C for 2 hours. The resulting particles had a D50 particle size of 25 μm and a span of 1.71. The average BET surface area of the resulting particles was 741 m 2 / g, the average pore volume is 2.55ml / g, and the average pore diameter is about
[0172] Example 5
[0173] The mesoporous silica material was obtained using an emulsion method. First, sodium silicate and acid were reacted to prepare a sol, and then oil and a surfactant were added to the sol to generate an emulsion. Sodium silicate (18 wt%) was added to an acid (136.3 g, 15.4 wt% H 2 SO 4) and mixed at 500rpm for 30 minutes to prepare a sol at a controlled temperature (≤25°C) and pH (about 1.5). A mixture of CX mineral oil (153.7g) and a surfactant (sorbitan monooleate, 8.4g) was added to the sol. An emulsion was prepared by continuous mixing at a speed of 400rpm for 25 minutes at ambient temperature. The pH was adjusted by adding 6g of ammonium hydroxide to the emulsion to control the gelation process of the sol. The emulsion was mixed for another 5 minutes at 250rpm. The temperature was then raised to 80°C without mixing and placed at 80°C for 1 hour. 400mL of water was then added and the mixture was mixed at 250rpm and 80°C for 1 hour. After the reaction, the mixture was cooled to separate the oil phase from the aqueous phase. The oil phase was separated and the particles were filtered out from the aqueous phase. The silica particles were then washed with 250ml of 80°C water while mixing at 250rpm for 30 minutes. The washing step was repeated twice more. The particles were then washed with isopropanol and the sample was subsequently dried in a vacuum oven at 60°C for 2 hours. The D50 particle size of the resulting particles was 26 μm and the span was 1.63. The average BET surface area of the resulting particles was 506 m 2 / g, the average pore volume is 1.91ml / g, and the average pore diameter is about
[0174] Example 6
[0175] The mesoporous silica material was obtained using an emulsion method. First, sodium silicate and acid were reacted to prepare a sol, which was then mixed with a surfactant and pumped into oil to form an emulsion. 275.68 g of sodium silicate (14 wt%) was added to an acid (50.14 g, 42 wt% H2O) at a flow rate of 10 ml / min. 2 SO 4) and mixed at 960rpm for 20 minutes to prepare a sol at a controlled temperature (≤25°C) and pH (1.81). A surfactant (sorbitan monooleate, 9.91g) was added to the sol and mixed at 960rpm for 5 minutes. The sol was then pumped into mineral oil (117.5g), and after the sol was completely pumped in, mixing continued at a speed of 960rpm for 10 minutes at a stable temperature (60°C) to form an emulsion. 300mL of deionized water was added to the emulsion. The pH was adjusted by adding 1.54g of 20% ammonium hydroxide and 200mL of water to the emulsion. The pH reached 2.5. Then 1.06g of 20% ammonium hydroxide and 10mL of water were added, and the pH reached 4.2. The temperature was raised to 80°C. The emulsion was then mixed at 250rpm for 1 hour. After the reaction, the mixture was left overnight to separate. The mixture was then filtered to separate the oil and surfactant from the silica particles. The silica particles were then washed using acidic water (pH ~4) at 80°C while mixing at 250 rpm for 90 minutes. The washing step was repeated two more times. The particles were then washed once with isopropanol and the sample was subsequently dried in a vacuum oven at 60°C for 1 hour. The BET surface area of the resulting particles was 526.2 m 2 / g, the average pore volume is 1.634ml / g, and the average pore diameter is
[0176] Example 7
[0177] The silica material with mesoporous structure is obtained using emulsion method. First, sodium silicate and acid are reacted to prepare sol, and then the sol is pumped into a mixture of surfactant and oil to generate emulsion. Sol is prepared by adding 201.35g sodium silicate (14 wt %) to acid (53.35g HCl (1:1)) at a flow rate of 10ml / min and mixing at 960rpm for 20 minutes. Surfactant (sorbitan monooleate, 7.61g) and 90.80g mineral oil are combined and mixed at 960rpm at 60°C. Then the sol is pumped into the mineral oil / surfactant mixture at a flow rate of 10mL / min, and after the sol is completely pumped in, it is continuously mixed at a speed of 960rpm for 10 minutes to form an emulsion at a stable temperature (60°C). 400mL deionized water is added to the emulsion. pH is adjusted by adding 1.01g 20% ammonium hydroxide to the emulsion. The temperature is raised to 80°C. The emulsion was then mixed at 250 rpm for 1 hour. After the reaction, the mixture was left overnight to separate. The mixture was then filtered to separate the oil and surfactant from the silica particles. The silica particles were then washed with 80°C acidic water (pH ~ 4) while mixing at 250 rpm for 90 minutes. The washing step was repeated two more times. The particles were then washed once with isopropanol and the sample was subsequently dried in a vacuum oven at 60°C for 1 hour. The BET surface area of the resulting particles was 480.04 m 2 / g, the average pore volume is 2.149ml / g, and the average pore diameter is
[0178] Example 8
[0179] In an argon atmosphere, 3.52 g of the silica particles (505 cm 2 / g SA, 2.53cc / g PV, PD) and 6.48g anhydrous toluene were mixed. MAO (30 wt %, 4.36g in toluene) was diluted with 7g toluene and slowly added to the silica support. The resulting mixture was stirred for 4 hours, then filtered and washed with 10mL toluene. After adding 10mL fresh toluene, 0.384g of a solution prepared from 0.771g of di(1-butyl-3-methylcyclopentadienyl)zirconium dichloride in 2.303g toluene was added to the stirred alkylated silica slurry. The mixture was stirred for 4 hours, filtered, washed with 15mL toluene, and then washed twice with 15mL heptane. The solid catalyst was dried under high vacuum for about 16 hours. ICP analysis of the catalyst: Al, 11.6 wt %, Zr, 0.42 wt %.
[0180] Example 9
[0181] Under an argon atmosphere, 3.54 g of the silica produced in Example 7 and 6.50 g of anhydrous toluene were mixed using a magnetic stirrer. MAO (30% by weight in toluene, 4.36 g) was diluted with 4 g of toluene and slowly added to the silica support. The resulting mixture was stirred for 4 hours, then filtered and washed with 10 mL of toluene. After adding 10 mL of fresh toluene, 0.386 g of a solution prepared from 0.771 g of di(1-butyl-3-methylcyclopentadienyl) zirconium dichloride in 2.303 g of toluene was added to the stirred alkylated silica slurry. The mixture was stirred for 4 hours, filtered, washed with 15 mL of toluene, and then washed twice with 15 mL of heptane. The solid catalyst was dried under high vacuum for about 16 hours. ICP analysis of the catalyst material: Al, 10.8 wt %, Zr, 0.34 wt %.
[0182] Example 10 (Comparative)
[0183] Under argon atmosphere, 3.45 g of Grace silica XPO-2538 (522 cm 2 / g SA, 1.86cc / g PV, PD) and 6.48g of anhydrous toluene were mixed. MAO (30 wt% in toluene, 4.42g) was diluted with 5g of toluene and slowly added to the silica support. The resulting mixture was stirred for 4 hours, then filtered and washed with 10mL of toluene. After adding 10mL of fresh toluene, 0.382g of a solution prepared from 0.771g of di(1-butyl-3-methylcyclopentadienyl)zirconium dichloride in 2.303g of toluene was added to the stirred alkylated silica slurry. The mixture was stirred for 4 hours, filtered, washed with 15mL of toluene, and then washed twice with 15mL of heptane. The solid catalyst was dried under high vacuum for about 16 hours. ICP analysis of the catalyst material: Al, 11.7 wt%; Zr, 0.40 wt%.
[0184] Embodiment 11
[0185] Dry sodium chloride (400 g) was charged to a reactor inerted with nitrogen and treated with 8 g of silica containing 10 wt% solid MAO as a scavenger. The reactor was heated to 50°C while stirring and 60 mg of the catalyst produced in Example 4 was added along with 2 mg of silica-MAO scavenger. The mixing rate was then increased. A mixture of ethylene, hydrogen and 1-hexene was added to a total pressure of 225 psi. The temperature was raised to 85°C and the polymerization was carried out for 1 hour. 2The molar ratio of ethylene / hexane was maintained at 0.0005 and the molar ratio of 1-hexane / ethylene was maintained at 0.028. The reactor was then depressurized and cooled to ambient temperature, after which the polymer was collected, washed with water to remove sodium chloride and silica, and dried under vacuum. SEM imaging showed mainly spherical resin particles. The particles were shown in Figure 8 Medium. Activity, 900g PE / g Cat; SBD, 0.45g / cc; MI (2.16kg), 0.36g / 10min, density, 0.928g / cc.
[0186] Example 12
[0187] The same procedure as in Example 8 was used, but using the silica produced in Example 5. SEM imaging showed predominantly spherical resin particles. Active, 1100 g PE / g Cat; SBD, 0.43 g / cc; MI (2.16 kg), 0.86 g / 10 min, Density, 0.931 g / cc.
[0188] Example 13
[0189] The same procedure as in Example 8 was used, but using the silica formed in Example 6. SEM imaging showed a granular morphology, mirroring that of the silica support, indicating very little loss during catalyst preparation and polymerization. Activity, 900 g PE / g Cat; SBD, 0.40 g / cc; MI (2.16 kg), 0.69 g / 10 min, density, 0.929 g / cc.
[0190] Example 14A
[0191] A portion of Example 4 was dried at 200°C for 4 hours (surface area 761 M 2 / g, pore volume 2.61cc / g, pore size 156 angstroms), then 10 grams were weighed into a 4 ounce plastic container, followed by the addition of 0.68 grams of chromium (III) acetylacetonate 97% (CrAcAc) to prepare a 1% Cr catalyst sample. The container was shaken for about 5 minutes to disperse the CrAcAc throughout the silica.
[0192] Example 14B
[0193] Activation of Cr Catalyst: 5 grams of Example 14A were placed in a quartz glass flask supported in a furnace. The flask was connected to a cylinder of subzero air with a flow rate of 52 liters / hour for fluidization. The furnace was programmed to reach a temperature of 1550°F (843°C) at a heating rate of 6.7°C. Once this temperature was reached, it was maintained for 6 hours. Upon completion, the flask was immediately removed from the furnace and allowed to cool to ambient temperature. The activated catalyst was transferred to a separate flask, which was then placed in a desiccator. The catalyst was analyzed by ICP to give a Cr content of 1.05%.
[0194] Example 14C
[0195] Activation of Cr Catalyst: 5 grams of Example 14A were placed in a quartz glass flask supported in a furnace. The flask was connected to a cylinder of subzero air with a flow rate of 52 liters / hour for fluidization. The furnace was programmed to reach a temperature of 1300°F (704.4°C) at a heating rate of 6.7°C. Once this temperature was reached, it was maintained for 5 hours. Upon completion, the flask was immediately removed from the furnace and allowed to cool to ambient temperature. The activated catalyst was transferred to a separate flask, which was then placed in a desiccator. The catalyst was analyzed by ICP to give a Cr content of 1.01%.
[0196] Example 15A
[0197] A portion of Example 5 was dried at 200°C for 4 hours (surface area 566 M 2 / g, pore volume 2.12cc / g, pore size 156 angstroms), then 10 grams were weighed into a 4 ounce plastic container, and then 0.68 grams of chromium (III) acetylacetonate 97% (CrAcAc) was added to prepare a 1% Cr catalyst sample. The container was shaken for about 5 minutes to disperse the CrAcAc throughout the silica.
[0198] Example 15B
[0199] Activation of Cr Catalyst: 5 grams of Example 15A were placed in a quartz glass flask supported in a furnace. The flask was connected to a cylinder of subzero air with a flow rate of 52 liters / hour for fluidization. The furnace was programmed to reach a temperature of 1550°F (843°C) at a heating rate of 6.7°C. Once this temperature was reached, it was maintained for 6 hours. Upon completion, the flask was immediately removed from the furnace and allowed to cool to ambient temperature. The activated catalyst was transferred to a separate flask, which was then placed in a desiccator. The catalyst was analyzed by ICP to give a Cr content of 0.98%.
[0200] Example 15C
[0201] Activation of Cr Catalyst: 5 grams of Example 15A were placed in a quartz glass flask supported in a furnace. The flask was connected to a cylinder of subzero air with a flow rate of 52 liters / hour for fluidization. The furnace was programmed to reach a temperature of 1300°F (704.4°C) at a heating rate of 6.7°C. Once this temperature was reached, it was maintained for 5 hours. Upon completion, the flask was immediately removed from the furnace and allowed to cool to ambient temperature. The activated catalyst was transferred to a separate flask, which was then placed in a desiccator. The catalyst was analyzed by ICP to give a Cr content of 0.98%.
[0202] Example 16A
[0203] 10 g of silica particles produced in Example 6 were calcined at 150° C. for 4 hours. 26.6 g of heptane was added to the calcined silica and mixed at ambient temperature to form a slurry. 1.14 g of TiPT (tetraisopropyl titanate) was then added to the slurry and mixed at room temperature for 30 minutes. The temperature was then raised to 40° C. for 3 hours, and the solvent was removed by vacuum to form a silica containing 2 wt % Ti. 10 g of 2 wt % Ti silica was weighed into a 4 oz plastic container, and 0.68 g of chromium (III) acetylacetonate 97% (CrAcAc) was then added to prepare a 1% Cr catalyst sample. The container was shaken for approximately 5 minutes to disperse the CrAcAc throughout the silica.
[0204] Example 16B
[0205] Activation of the Cr Catalyst: 5 grams of Example 16A were placed in a quartz glass flask supported in a furnace. The flask was connected to a cylinder of subzero air with a flow rate of 52 liters / hour for fluidization. The furnace was programmed to reach a temperature of 1550°F (843°C) at a heating rate of 6.7°C. Once this temperature was reached, it was maintained for 6 hours. Upon completion, the flask was immediately removed from the furnace and allowed to cool to ambient temperature. The activated catalyst was transferred to a separate flask, which was then placed in a desiccator. The catalyst was analyzed by ICP to give a Cr content of 1.10% and a Ti content of 2.15%.
[0206] Example 16C
[0207] Activation of the Cr Catalyst: 5 grams of Example 16A were placed in a quartz glass flask supported in a furnace. The flask was connected to a cylinder of subzero air with a flow rate of 52 liters / hour for fluidization. The furnace was programmed to reach a temperature of 1300°F (704.4°C) at a heating rate of 6.7°C. Once this temperature was reached, it was maintained for 5 hours. Upon completion, the flask was immediately removed from the furnace and allowed to cool to ambient temperature. The activated catalyst was transferred to a separate flask, which was then placed in a desiccator. The catalyst was analyzed by ICP to give a Cr content of 1.14% and a Ti content of 2.16%.
[0208] Embodiment 17
[0209] For polymerization testing of the Cr catalyst activated at 1550°F, 40mg-60mg of Cr catalyst sample was loaded into a 103°C reactor inerted with nitrogen. 1.25lbs of isobutane was added to the reactor to replace the nitrogen. The agitator was started and ethylene was added to bring the total pressure to 550psi. After 5 minutes, 4.5ml of 1-hexene was added to the reactor. Polymerization was carried out to achieve a productivity of 3600-4400g.PE / g catalyst. The reactor was then depressurized and cooled to ambient temperature, after which the polymer was collected and dried under vacuum for 7 minutes. Examples 14A, 15A and 16A were compared to Grace commercial reference HA30 (nominal 400M 2 / g surface area and 1.4cc / g pore volume) and HA30W (nominal 500M 2 The results of the pore volume (1.5 cc / g surface area) are listed in Table 2. The SEM image of the polymer fluff is shown in Figure 5-8 .
[0210] Table 2: Cr Catalyst Examples 14A, 15A and 16A Activated at 1550°F
[0211]
[0212] Embodiment 18
[0213] The 1300°F activated catalyst samples were polymerized at the target temperature and hexene amount to produce resins with a density of 0.9518-0.9530 and a melt index of 0.27-0.40. For these polymerizations, 40 mg-60 mg of sample was charged to a 102°C-105°C reactor inerted with nitrogen. 1.25 lbs of isobutane was added to the reactor to replace the nitrogen. The agitator was started and ethylene was added to bring the total pressure to 550 psi. After 5 minutes, 3.0-6.0 ml of 1-hexene was added to the reactor. Polymerizations were conducted to achieve a productivity of 3600-4400 g.PE / g catalyst. The reactor was then depressurized and allowed to cool to ambient temperature, after which the polymer was collected and dried under vacuum for 7 minutes. These resins were tested for environmental stress cracking resistance (ESCR) according to ASTM procedure #D1693-07a. The polymerization results are shown in Table 3.
[0214] Table 3: Cr Catalyst Example 16A Activated at 1300°F
[0215]
[0216] Embodiment 19
[0217] 13 g of spherical silica support (431 m 2 / g surface area, 2.19cc / g pore volume, 190 angstrom pore size and 1.15 span) were calcined at 500°C for 4 hours to produce a material containing less than 1% total volatiles. The material was transferred to a glove box and 10 grams were charged into a 500mL Schlenk flask and slurried in 110mL heptane. 13.3 grams of 20 wt% butylethylmagnesium in hexane were added dropwise to the silica slurry. The reaction mixture was transferred to a 1L autoclave reactor and stirred at 25°C for one hour. Anhydrous hydrogen chloride was bubbled through the reaction mixture for about two minutes until complete conversion was indicated by titration with 0.04% bromothymol blue. 0.99g TiCl 4 Added to the reactor, the reaction mixture was stirred at 25°C for one hour, then 36 mL of 1.0 M diethylaluminum chloride in hexane was slowly transferred to the procatalyst, resulting in a dark reddish brown color. The reaction mixture was stirred at 25°C for another 2 hours, then transferred to a Schlenk flask and dried under high vacuum at room temperature for 2 hours, resulting in 15 grams of catalyst.
[0218] 150 PSI of ethylene was charged to an inerted 2-L autoclave reactor at 50°C. 0.8 mL of 20% TEAL in heptane was combined with 40 mL of 1-hexene and pushed into the reactor under ethylene pressure along with 500 mL of isobutane, followed by the addition of 5 mg of the above catalyst in isohexane. After 215 PSI was quantitatively added from a 500 mL container, the reactor was stirred at 500 rpm and maintained at 50°C for 5 minutes. The reactor was heated to 85°C and an active ethylene stream was introduced to maintain a total pressure of 370 PSI. Polymerization was carried out for 1 hour, after which the reactor was depressurized and the resin was collected for analysis. SEM imaging showed a mixture of agglomerated and spherical resin particles. Activity, 6102 gPE / gCat; SBD, 0.25 g / cc; MI (2.16 kg) 1.23 g / 10 min.
[0219] Example 20 (Comparative)
[0220] 50 grams of a granular silica support (XPO-2538) was calcined at 600°C for 4 hours to produce a material containing less than 1% total volatiles. The material was transferred to a glove box and 15 grams were loaded into a 500 mL Schlenk flask and slurried in 90 mL heptane. 20.7 grams of 20 wt % butylethylmagnesium in hexane was added dropwise to the silica slurry. The reaction mixture was transferred to a 1 L autoclave reactor and stirred at 25°C for one hour. Anhydrous hydrogen chloride was bubbled through the reaction mixture for about two minutes until complete conversion was indicated by titration with 0.04% bromothymol blue. 1.5 g TiCl 4 Add to the reactor, stir the reaction mixture at 25°C for one hour, then slowly transfer 55mL1.0M diethylaluminum chloride in hexane to the primary catalyst, producing a dark reddish brown color. The reaction mixture was stirred at 25°C for another 2 hours, then transferred to a Schlenk flask and dried under high vacuum at room temperature for 2 hours, producing 22 grams of catalyst.
[0221] The same polymerization procedure as in Example 19 was used. SEM showed typical agglomerated morphology. Activity, 6217 gPE / gCat; SBD, 0.28 g / cc; MI (2.16 kg), 1.21 g / 10 min.
[0222] Embodiment 21
[0223] The mesoporous silica material was obtained using an emulsion method. First, sodium silicate and acid were reacted to prepare a sol, and then oil and a surfactant were added to the sol to generate an emulsion. Sodium silicate (18 wt%) was added to an acid (136.3 g, 15.4 wt% H 2 SO 4) and mixed at 500rpm for 30 minutes to prepare a sol at a controlled temperature (≤25°C) and pH (about 1.5). A mixture of CX mineral oil (153.7g) and a surfactant (sorbitan monooleate, 8.4g) was added to the sol. An emulsion was prepared by continuous mixing at a speed of 400rpm for 25 minutes at ambient temperature. The pH was adjusted by adding 6g of ammonium hydroxide to the emulsion to control the gelation process of the sol. The emulsion was mixed for another 5 minutes at 250rpm. The temperature was then raised to 80°C without mixing and placed at 80°C for 1 hour. 400mL of 10% by weight sulfuric acid was then added, and the mixture was mixed at 250rpm and 80°C for 1 hour. After the reaction, the mixture was cooled to separate the oil phase from the aqueous phase. The oil phase was separated and the particles were filtered out from the aqueous phase. The silica particles were then washed with 250ml of 80°C water while mixing at 250rpm for 30 minutes. The washing step was repeated twice more. The particles were then washed with isopropanol and the sample was subsequently dried in a vacuum oven at 60°C for 2 hours. The D50 particle size of the resulting particles was 32 μm. The average BET surface area of the resulting particles was 670 m 2 / g, and the average pore volume is 2.75ml / g.
[0224] Embodiment 22
[0225] Under argon atmosphere, 1.91g of spherical silica (calcined at 600°C) prepared according to Example 21 was added to a 20mL vial with a small stirrer and dispersed in 5mL toluene. While gently stirring the silica slurry, MAO (4.4g 30% toluene solution) was added dropwise. The mixture was stirred for 2 hours and then allowed to settle. The supernatant was decanted and 5mL toluene was added, and the washing procedure was then repeated. Rac-dimethylsilylene bis(2-methylindenyl) zirconium dichloride (0.031g) was dissolved in 1mL toluene and added dropwise to the silica suspension under gentle stirring, allowing stirring for 1 hour. The catalyst was separated by filtration and washed with toluene, then dried under high vacuum. ICP analysis of the catalyst: Al, 16.5% by weight, Zr, 0.17% by weight.
[0226] Example 23 (Comparative)
[0227] The catalyst was prepared in the same manner as Example 22, except that a spray-dried spherical silica support was used, which had a d50 of 27 μm, a 2 / g SA, 1.6cc / g PV.
[0228] Embodiment 24
[0229] A 2L autoclave reactor was purged with argon at over 100°C and then flushed with liquid propylene. Under an argon atmosphere, 0.5 mL of 25% triethylaluminum in heptane and 3 mL of additional heptane were added to a feed container and the mixture was flushed into the prepared autoclave with 600 mL of propylene. The temperature was raised to 70°C and stirring was started. Under an argon atmosphere, approximately 100 mg of the catalyst prepared according to Example 22 was weighed into another feed container and dispersed in 5 mL of heptane. The catalyst was flushed into the autoclave reactor with 450 mL of propylene and the reaction was allowed to proceed for 1 hour after reaching 70°C. The autoclave was then cooled to below 25°C and vented to collect the polymer and dry it under a stream of air. Activity, 3500 gPP / gCat; SBD, 0.42 g / cc. The polypropylene resin has a viscosity of Fig. 9 The spherical morphology shown.
[0230] Example 25 (Comparative)
[0231] The same propylene polymerization procedure as outlined in Example 24 was followed using the catalyst prepared according to Example 25. Activity, 2300 gPP / gCat; SBD, 0.43 g / cc. The polypropylene resin had Fig.10 A mixture of spherical and irregular morphologies is shown.
[0232] Paragraph 1. An olefin polymerization catalyst system comprising a silica support, a catalyst precursor compound and an activator, wherein the silica support comprises a plurality of silica gel particles, wherein: each particle comprises a rigid network of amorphous silica; the particles are spherical single-particle gel particles; the average aspect ratio of the particles is about 1.2 or less; the average pore volume of the particles is about 1.4 ml / g to about 3 ml / g; the average surface area of the particles is about 200 m 2 / g to about 950m 2 / g; the median particle size of the particles is about 4 μm to about 100 μm.
[0233] Paragraph 2. The olefin polymerization catalyst system according to Paragraph 1, wherein at least 75% of the particles have an aspect ratio of about 1.2 or less.
[0234] Paragraph 3. An olefin polymerization catalyst system according to paragraph 1 or 2, wherein at least 50% of the particles have an aspect ratio of about 1.1 or less.
[0235] Paragraph 4. The olefin polymerization catalyst system according to any of paragraphs 1-3, wherein the catalyst precursor compound comprises a metallocene component.
[0236] Paragraph 5. The olefin polymerization catalyst system according to any of paragraphs 1-4, wherein the activator comprises an organoaluminum compound.
[0237] Paragraph 6. The olefin polymerization catalyst system according to any of paragraphs 1-5, wherein the activator comprises an aluminoxane.
[0238] Paragraph 7. The olefin polymerization catalyst system according to any of paragraphs 1-6, wherein the activator comprises a borane or a borate.
[0239] Paragraph 8. An olefin polymerization catalyst system according to any of paragraphs 1-7, wherein the number percentage of silica particles having a particle size of 1 μm or less is about 1% or less.
[0240] Paragraph 9. An olefin polymerization catalyst system according to any of paragraphs 1-8, wherein the silica particles have not undergone spray drying agglomeration.
[0241] Paragraph 10. An olefin polymerization catalyst system according to any of paragraphs 1-9, wherein the silica particles have an average pore size of about 30 angstroms to about 300 angstroms.
[0242] Paragraph 11. An olefin polymerization catalyst system according to any of paragraphs 1-10, wherein the silica particles have an average pore size of about 100 to about 240 angstroms.
[0243] Paragraph 12. The olefin polymerization catalyst system of any of paragraphs 1-11, wherein the silica particles have a span of about 1.5 or less.
[0244] Paragraph 13. An olefin polymerization catalyst system according to any of paragraphs 1-12, wherein the silica particles have a span of 0.9 or greater.
[0245] Paragraph 14. The olefin polymerization catalyst system of any of paragraphs 1-13, wherein the activator comprises an organoaluminum compound and is supported on a carrier such that the catalyst system contains about 10 wt% or more Al.
[0246] Paragraph 15. An olefin polymerization catalyst system according to any one of paragraphs 1 to 4, wherein the particles have an average pore volume greater than 2.3 ml / g and a pore volume greater than 350 m 2 / g average pore size.
[0247] Paragraph 16. An olefin polymerization catalyst system according to any of paragraphs 1-15, wherein the silica particles have a median particle size of about 5 μm to about 60 μm.
[0248] Paragraph 17. An olefin polymerization catalyst system comprising a silica support and a chromium compound, wherein the silica support comprises a plurality of silica gel particles, wherein: each particle comprises a rigid network of amorphous silica; the particles are spherical single-particle gel particles; the average aspect ratio of the particles is about 1.2 or less; the average pore volume of the particles is about 1.4 ml / g to about 3 ml / g; the average surface area of the particles is about 200 m 2 / g to about 950m 2 / g; the median particle size of the particles is about 4 μm to about 100 μm.
[0249] Paragraph 18. The olefin polymerization catalyst system according to paragraph 17, wherein at least 75% of the particles have an aspect ratio of about 1.2 or less.
[0250] Paragraph 19. The olefin polymerization catalyst system according to paragraph 17 or 18, wherein at least 50% of the particles have an aspect ratio of about 1.1 or less.
[0251] Paragraph 20. The olefin polymerization catalyst system according to any of paragraphs 17-19, wherein the chromium compound is chromium oxide.
[0252] Paragraph 21. The olefin polymerization catalyst system according to any of paragraphs 17-20, wherein the chromium compound is a chromium salt.
[0253] Paragraph 22. The olefin polymerization catalyst system according to any of paragraphs 17-21, further comprising a titanium compound, an aluminum compound, or a fluorine compound impregnated on a silica support.
[0254] Paragraph 23. An olefin polymerization catalyst system according to any of paragraphs 17-22, wherein the number percentage of silica particles having a particle size of 1 μm or less is about 1% or less.
[0255] Paragraph 24. An olefin polymerization catalyst system according to any of paragraphs 17-23, wherein the silica particles have not undergone spray drying agglomeration.
[0256] Paragraph 25. An olefin polymerization catalyst system according to any of paragraphs 17-24, wherein the silica particles have an average pore size of about 30 angstroms to about 300 angstroms.
[0257] Paragraph 26. An olefin polymerization catalyst system according to any of paragraphs 17-25, wherein the silica particles have an average pore size of about 100 to about 240 angstroms.
[0258] Paragraph 27. An olefin polymerization catalyst system according to any of paragraphs 17-26, wherein the silica particles have a span of about 1.5 or less.
[0259] Paragraph 28. An olefin polymerization catalyst system according to any of paragraphs 17-27, wherein the silica particles have a span of 0.9 or greater.
[0260] Paragraph 29. An olefin polymerization catalyst system according to any one of paragraphs 17-28, wherein the particles have an average pore volume greater than 2.3 ml / g and a pore volume greater than 350 m 2 / g average pore size.
[0261] Paragraph 30. An olefin polymerization catalyst system according to any of paragraphs 17-29, wherein the silica particles have a median particle size of about 5 μm to about 60 μm.
[0262] Paragraph 31. An olefin polymerization catalyst system comprising a silica support, a magnesium halide, a transition metal compound, a cocatalyst and an electron donor compound, wherein the silica support comprises a plurality of silica gel particles, wherein: each particle comprises a rigid network of amorphous silica; the particles are spherical single-particle gel particles; the average aspect ratio of the particles is about 1.2 or less; the average pore volume of the particles is about 1.4 ml / g to about 3 ml / g; the average surface area of the particles is about 200 m 2 / g to about 950m 2 / g; the median particle size of the particles is about 4 μm to about 100 μm.
[0263] Paragraph 32. The olefin polymerization catalyst system of paragraph 31, wherein at least 75% of the particles have an aspect ratio of about 1.2 or less.
[0264] Paragraph 33. The olefin polymerization catalyst system of paragraph 31 or 32, wherein at least 50% of the particles have an aspect ratio of about 1.1 or less.
[0265] Paragraph 34. The olefin polymerization catalyst system according to any of paragraphs 31-33, wherein the transition metal compound is a Group 4 metal compound.
[0266] Paragraph 35. The olefin polymerization catalyst system according to any of paragraphs 31-34, wherein the electron donor compound is an internal electron donor compound.
[0267] Paragraph 36. The olefin polymerization catalyst system according to any of paragraphs 31-35, wherein the electron donor compound is an external electron donor compound.
[0268] Paragraph 37. An olefin polymerization catalyst system according to any of paragraphs 31-36, wherein the number percentage of silica particles having a particle size of 1 μm or less is about 1% or less.
[0269] Paragraph 38. An olefin polymerization catalyst system according to any of paragraphs 31-37, wherein the silica particles have not undergone spray drying agglomeration.
[0270] Paragraph 39. An olefin polymerization catalyst system according to any of paragraphs 31-38, wherein the silica particles have an average pore size of about 30 angstroms to about 300 angstroms.
[0271] Paragraph 40. An olefin polymerization catalyst system according to any of paragraphs 31-39, wherein the silica particles have an average pore size of about 100 to about 240 angstroms.
[0272] Paragraph 41. An olefin polymerization catalyst system according to any of paragraphs 31-40, wherein the silica particles have a span of about 1.5 or less.
[0273] Paragraph 42. An olefin polymerization catalyst system according to any of paragraphs 31-41, wherein the silica particles have a span of 0.9 or greater.
[0274] Paragraph 43. An olefin polymerization catalyst system according to any of paragraphs 31-42, wherein the particles have an average pore volume greater than 2.3 ml / g and a pore volume greater than 350 m 2 / g average pore size.
[0275] Paragraph 44. An olefin polymerization catalyst system according to any of paragraphs 31-43, wherein the silica particles have a median particle size of about 5 μm to about 60 μm.
[0276] Paragraph 45. A method for polymerizing olefins, the method comprising contacting an olefin monomer with a catalyst system comprising a silica support and a catalyst precursor compound to form polyolefin particles, the silica support comprising a plurality of silica gel particles, wherein: each particle comprises a rigid network of amorphous silica; the particles are spherical single-particle gel particles; the particles have an average aspect ratio of about 1.2 or less; the particles have an average pore volume of about 1.4 ml / g to about 3 ml / g; the particles have an average surface area of about 200 m 2 / g to about 950m 2 / g; the median particle size of the particles is about 4 μm to about 100 μm.
[0277] Paragraph 46. The method of Paragraph 45, wherein the resulting polyolefin particles have a particle size distribution such that the number percentage of particles having a particle size of 1 μm or less is about 1% or less.
[0278] Paragraph 47. The process of paragraph 45 or 46, wherein the olefin is polymerized in a gas phase reactor.
[0279] Paragraph 48. The method of any of paragraphs 45-47, wherein the polyolefin particles have a settled bulk density greater than 0.4 g / cc.
[0280] Paragraph 49. The method of any of paragraphs 45-48, wherein the polyolefin particles have an aspect ratio of about 1.2 or less.
[0281] Paragraph 50. The method of any of Paragraphs 45-49, wherein at least 75% of the particles have an aspect ratio of about 1.2 or less.
[0282] Paragraph 51. The method of any of paragraphs 45-50, wherein at least 50% of the particles have an aspect ratio of about 1.1 or less.
[0283] Paragraph 52. The method of any of paragraphs 45-51, wherein the polyolefin comprises polyethylene.
[0284] Paragraph 53. The method of any of paragraphs 45-52, wherein the polyolefin comprises polypropylene.
[0285] Paragraph 54. The method of any of paragraphs 45-53, wherein the polyolefin comprises a poly-alpha-olefin.
[0286] Those of ordinary skill in the art may make these and other modifications and changes to the present invention without departing from the spirit and scope of the present invention, which are more specifically described in the appended claims. In addition, it should be understood that the aspects of the various embodiments may be interchangeable in whole or in part. In addition, those of ordinary skill in the art will appreciate that the above description is merely illustrative and is not intended to limit the present invention, which is further described in the appended claims.
[0287] While certain embodiments have been illustrated and described, it will be appreciated that changes and modifications may be made therein in accordance with ordinary skill in the art without departing from the technology in its broader aspects as defined by the following claims.
[0288] The embodiments exemplarily described herein may be appropriately implemented in the absence of any one or more elements, one or more limitations not specifically disclosed herein. Therefore, for example, the terms "comprise", "include", "contain", etc. should be widely understood and unrestricted. In addition, the terms and expressions used herein have been used as descriptive terms rather than limiting terms, and the use of such terms and expressions is not intended to exclude any equivalents of the features shown and described or parts thereof, but it should be recognized that various modifications can be made within the scope of the claimed technology. In addition, the phrase "essentially consisting of..." should be understood to include those elements specifically enumerated and those additional elements that will not have a substantial impact on the basic features and novel features of the claimed technology. The phrase "consisting of..." excludes any unspecified elements.
[0289] The present disclosure is not limited to the specific embodiments described in this application. It will be appreciated by those skilled in the art that many modifications and variations may be made without departing from its spirit and scope. In addition to those listed herein, those skilled in the art will appreciate from the foregoing description that functionally equivalent methods and compositions within the scope of the present disclosure. Such modifications and variations are intended to fall within the scope of the appended claims. The present disclosure is limited only by the terms of the appended claims and the full range of equivalents enjoyed by such claims. It should be understood that the present disclosure is not limited to specific methods, reagents, compounds, compositions or biological systems, which may of course vary. It should also be understood that the terms used herein are only used to describe specific embodiments and are not intended to be limiting.
[0290] In addition, where features or aspects of the disclosure are described in terms of Markush groups, those skilled in the art will recognize that the disclosure is also thereby described in terms of any individual member or subgroup of members of the Markush group.
[0291] Those skilled in the art will appreciate that, for any and all purposes, particularly in providing a written description, all ranges disclosed herein also encompass any and all possible subranges and combinations of subranges thereof. Any listed range can be easily understood to fully describe and be able to decompose the same range into at least equal halves, thirds, quarters, fifths, tenths, etc. As a non-limiting example, each range discussed herein can be easily decomposed into a lower third, a middle third, and an upper third, etc. Those skilled in the art will also appreciate that all language, such as "at most," "at least," "greater than," "less than," etc., includes the numbers listed and refers to a range that can be subsequently decomposed into subranges as discussed above. Finally, those skilled in the art will appreciate that a range includes each individual member.
[0292] All publications, patent applications, issued patents, and other documents mentioned in this specification are incorporated herein by reference, as if each individual publication, patent application, issued patent, or other document was specifically and individually indicated to be incorporated by reference in its entirety. Definitions contained in text incorporated by reference are excluded to the extent they conflict with definitions in this disclosure.
[0293] Other embodiments are set forth in the following claims.
Claims
1. An olefin polymerization catalyst system, comprising a silica carrier, a catalyst precursor compound and an activator, wherein the silica carrier comprises a plurality of silica gel particles, wherein: Each particle consists of a rigid network of amorphous silica; The particles are spherical single-particle gel particles; The particles have an average aspect ratio of about 1.2 or less; The particles have an average pore volume of about 1.4 ml / g to about 3 ml / g; The particles have a diameter of about 200 m 2 / g to about 950m 2 The average surface area of / g; and The particles have a median particle size of about 4 μm to about 100 μm.
2. The olefin polymerization catalyst system of claim 1, wherein at least 75% of the particles have an aspect ratio of about 1.2 or less.
3. The olefin polymerization catalyst system of claim 1, wherein at least 50% of the particles have an aspect ratio of about 1.1 or less.
4. The olefin polymerization catalyst system according to claim 1, wherein the catalyst precursor compound comprises a metallocene component.
5. The olefin polymerization catalyst system according to claim 1, wherein the activator comprises an organoaluminum compound.
6. The olefin polymerization catalyst system of claim 1, wherein the activator comprises aluminoxane.
7. The olefin polymerization catalyst system of claim 1, wherein the activator comprises borane or borate.
8. The olefin polymerization catalyst system of claim 1, wherein the number percentage of silica particles having a particle size of 1 μm or less is about 1% or less.
9. The olefin polymerization catalyst system of claim 1, wherein the silica particles have not been subjected to spray drying agglomeration.
10. The olefin polymerization catalyst system of claim 1, wherein the silica particles have an average pore size of about 30 angstroms to about 300 angstroms.
11. The olefin polymerization catalyst system of claim 1, wherein the silica particles have an average pore size of about 100 to about 240 angstroms.
12. The olefin polymerization catalyst system of claim 1, wherein the silica particles have a span of about 1.5 or less.
13. The olefin polymerization catalyst system according to claim 1, wherein the silica particles have a span of 0.9 or more.
14. The olefin polymerization catalyst system of claim 1, wherein the activator comprises an organoaluminum compound and is supported on a carrier such that the catalyst system contains about 10 wt% or more of Al.
15. The olefin polymerization catalyst system according to claim 1, wherein the particles have an average pore volume greater than 2.3 ml / g and a pore volume greater than 350 m 2 / g average pore size.
16. The olefin polymerization catalyst system of claim 1, wherein the silica particles have a median particle size of about 5 μm to about 60 μm.
17. An olefin polymerization catalyst system comprising a silica support and a chromium compound, wherein the silica support comprises a plurality of silica gel particles, wherein: Each particle consists of a rigid network of amorphous silica; The particles are spherical single-particle gel particles; The particles have an average aspect ratio of about 1.2 or less; The particles have an average pore volume of about 1.4 ml / g to about 3 ml / g; The particles have a diameter of about 200 m 2 / g to about 950m 2 The average surface area of / g; and The particles have a median particle size of about 4 μm to about 100 μm.
18. The olefin polymerization catalyst system of claim 17, wherein at least 75% of the particles have an aspect ratio of about 1.2 or less.
19. The olefin polymerization catalyst system of claim 17, wherein at least 50% of the particles have an aspect ratio of about 1.1 or less.
20. The olefin polymerization catalyst system according to claim 17, wherein the chromium compound is chromium oxide.
21. The olefin polymerization catalyst system according to claim 19, wherein the chromium compound is a chromium salt.
22. The olefin polymerization catalyst system according to claim 17, further comprising a titanium compound, an aluminum compound or a fluorine compound impregnated on a silica support.
23. The olefin polymerization catalyst system of claim 17, wherein the number percentage of silica particles having a particle size of 1 μm or less is about 1% or less.
24. The olefin polymerization catalyst system of claim 17, wherein the silica particles have not undergone spray drying agglomeration.
25. The olefin polymerization catalyst system of claim 17, wherein the silica particles have an average pore size of about 30 angstroms to about 300 angstroms.
26. The olefin polymerization catalyst system of claim 17, wherein the silica particles have an average pore size of about 100 to about 240 angstroms.
27. The olefin polymerization catalyst system of claim 17, wherein the silica particles have a span of about 1.5 or less.
28. The olefin polymerization catalyst system of claim 17, wherein the silica particles have a span of 0.9 or more.
29. The olefin polymerization catalyst system of claim 17, wherein the particles have an average pore volume greater than 2.3 ml / g and a pore volume greater than 350 m 2 / g average pore size.
30. The olefin polymerization catalyst system of claim 17, wherein the silica particles have a median particle size of about 5 μm to about 60 μm.
31. An olefin polymerization catalyst system comprising a silica support, a magnesium halide, a transition metal compound, a co-catalyst and an electron donor compound, wherein the silica support comprises a plurality of silica gel particles, wherein: Each particle consists of a rigid network of amorphous silica; The particles are spherical single-particle gel particles; The particles have an average aspect ratio of about 1.2 or less; The particles have an average pore volume of about 1.4 ml / g to about 3 ml / g; The particles have a diameter of about 200 m 2 / g to about 950m 2 The average surface area of / g; and The particles have a median particle size of about 4 μm to about 100 μm.
32. The olefin polymerization catalyst system of claim 31, wherein at least 75% of the particles have an aspect ratio of about 1.2 or less.
33. The olefin polymerization catalyst system of claim 31, wherein at least 50% of the particles have an aspect ratio of about 1.1 or less.
34. The olefin polymerization catalyst system of claim 31, wherein the transition metal compound is a Group 4 metal compound.
35. The olefin polymerization catalyst system of claim 31, wherein the electron donor compound is an internal electron donor compound.
36. The olefin polymerization catalyst system according to claim 31, wherein the electron donor compound is an external electron donor compound.
37. The olefin polymerization catalyst system of claim 31, wherein the number percentage of silica particles having a particle size of 1 μm or less is about 1% or less.
38. The olefin polymerization catalyst system of claim 31, wherein the silica particles have not undergone spray drying agglomeration.
39. The olefin polymerization catalyst system of claim 31, wherein the silica particles have an average pore size of about 30 angstroms to about 300 angstroms.
40. The olefin polymerization catalyst system of claim 31, wherein the silica particles have an average pore size of about 100 to about 240 angstroms.
41. The olefin polymerization catalyst system of claim 31 , wherein the silica particles have a span of about 1.5 or less.
42. The olefin polymerization catalyst system of claim 31, wherein the silica particles have a span of 0.9 or greater.
43. The olefin polymerization catalyst system of claim 31, wherein the particles have an average pore volume greater than 2.3 ml / g and a pore volume greater than 350 m 2 / g average pore size.
44. The olefin polymerization catalyst system of claim 31, wherein the silica particles have a median particle size of about 5 μm to about 60 μm.
45. A method of polymerizing an olefin, the method comprising contacting an olefin monomer with a catalyst system comprising a silica support and a catalyst precursor compound to form polyolefin particles, the silica support comprising a plurality of silica gel particles, wherein: Each particle consists of a rigid network of amorphous silica; The particles are spherical single-particle gel particles; The particles have an average aspect ratio of about 1.2 or less; The particles have an average pore volume of about 1.4 ml / g to about 3 ml / g; The particles have a diameter of about 200 m 2 / g to about 950m 2 The average surface area of / g; and The particles have a median particle size of about 4 μm to about 100 μm.
46. The method of claim 45, wherein the resulting polyolefin particles have a particle size distribution wherein the number percentage of particles having a particle size of 1 μm or less is about 1% or less.
47. The process of claim 45, wherein the olefin is polymerized in a gas phase reactor.
48. The method of claim 45, wherein the polyolefin particles have a settled bulk density greater than 0.4 g / cc.
49. The method of claim 45, wherein the polyolefin particles have an aspect ratio of about 1.2 or less.
50. The olefin polymerization catalyst system of claim 45, wherein at least 75% of the particles have an aspect ratio of about 1.2 or less.
51. The olefin polymerization catalyst system of claim 45, wherein at least 50% of the particles have an aspect ratio of about 1.1 or less.
52. The method of claim 45, wherein the polyolefin comprises polyethylene.
53. The method of claim 45, wherein the polyolefin comprises polypropylene.
54. The method of claim 45, wherein the polyolefin comprises a polyalphaolefin.
Citation Information
Patent Citations
Polymerization of olefins in the presence of a supported catalyst
US5633419A
Procatalyst composition with substituted 1,2-phenylene aromatic diester internal donor and method
US8536372B2